Biomass-derived biochar for CO2 adsorption: Physicochemical design, adsorption kinetics, isotherm modeling, and carbon-management perspectives - Baala H. Anandapadmanaban; Shu-Hui Liu; Chi-Wen Lin; Tzung-Han Chou; Rabia Tasaduq Hussain (Biomass and Bioenergy, 2027)

Mitigation of membrane biofouling by a novel Pseudomonas knackmussii HITSZ-Q1 immobilized in biochar-reinforced beads: Quenching mechanism and MBR performance - Wen-Qian Wang; Jian-Hui Chen; Shen Liang; Qi-Shi Si; Jun-Yan Kuang; Hong-Tao Shi; Chen-Yi Jiang; Xin-Ying Wang; Song-Fang Han; Xiao-Chi Feng; Nan-Qi Ren (Bioresource Technology, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Multi-objective optimization of horizontal-axis tidal current turbine blades for enhanced energy extraction and operational stability - Yiyuan Zhang; Haoran Yang; Qianzheng Liang; Zhen Gao; Chi Zhang; Dai Zhou; Zhaolong Han (Ocean Engineering, 2026)

Process-oriented design of 3D-printed Fe–Co/biochar cathodes for mass-transfer-enhanced bioelectro-Fenton degradation of bisphenol A - Chi-Wen Lin; Shih-Hao Liu; Chung-Yen Yeh; Tzung-Han Chou; Shu-Hui Liu (Journal of Water Process Engineering, 2026)

High-resolution spatiotemporal monitoring of chlorophyll-a in small inland reservoirs using multi-source remote sensing data fusion - Pengfei Han; Jian Wu; Jingjing Wu; Wei Wang; Chi Zhang; Zhuohang Xin (Journal of Hydrology, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Chemometrics and machine learning for efficient grading and sensory prediction of raw milk flavor - Yanmei Xi; Xuelu Chi; Lunaike Zhao; Weizhe Wang; Jianfeng Wang; Jiyu Han; Yufang Su; Baoguo Sun; Nasi Ai (Food Research International, 2026)

Cyclocarya paliurus polyphenols from deep eutectic solvent extraction alleviate glucose metabolic disorders via PI3K/akt-mediated autophagy - Xiao Han; Yiting Tang; Kyawt Nay Chi Tun; Fujie Yan (Food Bioscience, 2026)

Immune response as a modifier linking phthalate exposure to lung function decline: Results from a longitudinal study - Wei-Chi Wang; Yuan-Ting C. Lo; Hsiu-Ying Ku; Hsu-Kai Huang; You-Zhen Chen; Wei-Yu Lin; Han-Bin Huang (Environmental Pollution, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Stable photocatalytic CO2-to-CH4 conversion enabled by a 3D hydrophobic Ti3C2Tx MXene architecture under continuous flow - Hyunju Jung; Eunji Kim; Chi Won Ahn; Hee Han; Issam Gereige; Aqil Jamal; Yonghee Lee; Hee-Tae Jung (Chemical Engineering Journal, 2026)

Capsaicin alleviates mitochondrial dysfunction in skeletal muscle of obese mice and C2C12 myotubes via the involvement of clock gene - Liguang Han; Chi-Tang Ho; Zixiang Ye; Hengye Zhang; Chuyao Zong; Xingran Kou; Muwen Lu (Food Bioscience, 2026)

Dosage and timing both matter: Promoting favorable microbial interactions in carrier-enhanced microalgal-bacterial granules by external bicarbonate - Jian-Xia Wang; Liu Yang; Xiang-Yi Kong; Jing-Han Wang; Zhan-You Chi; Jian-Gang Ren (Chemical Engineering Journal, 2026)

A novel phosphorylated chitin-hydroxyapatite composite promotes angiogenesis and osteogenesis for bone defect repair - Zhen Jiang; Siheng Niu; Wei Zhang; Zhiwen Jiang; Jinhua Chi; Shouriu Liu; Wanshun Liu; Shuo Wang; Baoqin Han (Carbohydrate Polymers, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

How alternate wetting and drying irrigation drives carbon reduction in rice-crab cocultural ecosystem: A quantitative assessment - Hongwei Han; Yikui Bai; Feng Zhang; Haixia Liu; Yijian Tong; Daocai Chi; Taotao Chen (Agriculture, Ecosystems & Environment, 2026)

Flow-induced vibro-acoustic response of a rim-driven thruster under oblique inflow - Yin Han; Xudong Li; Jing Fang; Chi Zhang; Yilin Qu (Ocean Engineering, 2026)

Nitrogen in light-industrial biowastes: From functional characterization to thermochemical regulation strategies - Chi Xu; Boyu Han; Shihao Meng; Ayipaiyili Yuetikuer; Hao Zhan; Xingbang Wan; Fangfang Zhu; Lijian Leng; Zhiyong Zeng; Hailong Li (Journal of Cleaner Production, 2026)

Exploring genetic structure and habitat suitability of the masked palm civet (Paguma larvata) in Taiwan - Shih-Wei Chang; Tzong-Han Lin; Chi-Li Tsai; Hui-Yun Tseng (Mammalian Biology, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Metallogenic Mechanism for the Deep Part of the Jiaojia Gold Zone in the Eastern North China Craton (Jiaodong): Constrains from Pyrite Re-Os Geochronology, in-situ Trace Elements and Sulfur Isotope Compositions - Naijie Chi; Zuozhen Han; Xuefeng Yu; Wei Shan; Chuan’e Liu; Xiufeng Wang; Zengsheng Li; Shenghu Li; Chenxi Zhang; Xiangxian Ma (Journal of Earth Science, 2026)

Strategic selection of nuclear fuel cycle backend options: A framework incorporating MA separation and final disposal by multi-criteria evaluation - Masahiko Nakase; Tatsuro Matsumura; Ryo Hamada; Chi Young Han; Go Chiba; Tomofumi Sakuragi; Hidekazu Asano (Annals of Nuclear Energy, 2026)

Feasibility of a PET/MR Imaging Workflow in Adult Zebrafish Using Intracardiac FDG Injection - Chi-Yu Lai; Avery Landon Wang; Chi-Han Wu; Guor-Mour Her; Skye Hsin-Hsien Yeh; Wen-Tao Huang; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2026)
Purpose In vivo imaging of adult zebrafish remains technically challenging due to loss of optical transparency and the lack of standardized molecular imaging protocols. The development of reliable radiotracer delivery and acquisition parameters is essential for improving imaging reproducibility and translational relevance. Methods Adult zebrafish with hepatobiliary tumor models were imaged using an integrated PET/MR system following intracardiac injection of F-18 FDG. Animals were assigned to four groups based primarily on uptake time, ranging from approximately 40 to 90 min, with injected activity maintained within a narrow range. A standardized imaging workflow, including anesthesia, positioning, PET acquisition, and MRI co-registration, was implemented. Image quality, tracer distribution, and tumor visualization were qualitatively compared across groups. Results Intracardiac injection provided reliable systemic tracer delivery across all groups. Short uptake times resulted in high background activity, particularly in the gastrointestinal tract, while prolonged uptake times led to signal decay. An intermediate uptake time (~ 60 min) appeared to provide the most favorable balance between signal intensity and background suppression under the current experimental setting. MRI consistently delineated hepatic lesions, while PET signal quality varied depending on protocol parameters. Semi-quantitative analysis indicated higher tracer uptake in lesion regions relative to adjacent background tissue. Conclusion This study establishes the first feasible PET/MR imaging workflow and identifies preliminary imaging conditions for adult zebrafish, demonstrating that uptake time is a critical determinant of imaging quality. The proposed workflow provides a reproducible platform for longitudinal in vivo imaging and may serve as a practical intermediate platform for preclinical molecular imaging prior to rodent studies.

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

Crack propagation and coalescence of ice with flaws under SHPB impact loading: Experimental investigation and peridynamic simulation - Chen Chi; Yiheng Zhang; Ying Tang; Xiaobin Li; Wei Chen; Qing Wang; Duanfeng Han; Yinggang Li (Ocean Engineering, 2026)

Temperature-dependent regulation of benzeneacetaldehyde formation during black tea drying: Evidence from non-targeted metabolomics and an EGCG-modulated Maillard reaction model - Zisheng Han; Shengxiao Su; Wen Li; Tong Jia; Piaopiao Long; Jia-Ping Ke; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2026)

Rice-crab co-culture mitigates reactive gaseous N losses and increases economic benefits - Feng Zhang; Guimin Xia; Yuanze Qiu; Hongwei Han; Haixia Liu; Benji Yi; Bohao Li; Daocai Chi; Taotao Chen (Field Crops Research, 2026)

Fe/FeF2 Mott-Schottky heterojunction with the spontaneous charge transfer boosting the bifunctional oxygen electrocatalysis performance - Nanping Deng; Jinyu Han; Hao Chi; Yewen Shui; Xinyi Li; Chengwei Liu; Gang Wang; Weimin Kang; Bowen Cheng (Chemical Engineering Journal, 2026)

Extracting cropping patterns from remotely sensed images in a mixed single-, double-, and triple-cropping region of Southern China - Yifan Li; Chen Cheng; Xiaoming Shi; Hong Chi; Yifei Han; Fei Zhao; Jinliang Huang; Feng Ling (Environmental Monitoring and Assessment, 2026)

Drying temperature and ethanol extraction parameters of calamondin peel and their effects on flavonoid composition, in vitro antioxidant capacity and anti-lipid accumulation efficacy - Yun-Shan Han; Yu Chen; Chi-Tang Ho; Yen-Chen Tung (South African Journal of Botany, 2026)

Completing the puzzle of aged microplastics towards microalgae at environmental concentration: effects of polymer type, size, aging method, and aging duration - Ming-Zhi Shen; Liu Yang; Yi-Ran Zhai; Jing-Han Wang; Zhan-You Chi; Qiang Zhang (Journal of Cleaner Production, 2026)

Coupling virtual and physical water optimization: a bi-level stochastic model for basin water scarcity mitigation - Wei Li; Hao Yang; Mingshuai Chen; Jiajun Cui; Junlong Zhang; Chi Han; Li You; Yongping Li; Guohe Huang (Journal of Cleaner Production, 2026)

Integration of AHRR methylation, heavy metals, and clinical characteristics for urothelial carcinoma risk stratification: An explainable artificial intelligence approach - Chia-Min Chung; Chao-Hsiang Chang; Chin-Huai Chang; Wen-Chi Chang; Yi-Huei Chang; Po-Jen Hsiao; Chi-Shun Lien; Han Chang; Mu-Chi Chung; Chi-Jung Chung (Environmental Pollution, 2026)

Enhancement of microalgal biofilm growth and atmospheric CO2 capture by metal-organic frameworks (MOFs): Influences of MOF type, dosage, and calcination conditions - Tong Wu; Yi-Ran Zhai; Jing-Han Wang; Zhan-You Chi; Jian-Gang Ren (Chemical Engineering Journal, 2026)

Response of a heterotrophic denitrification system to aminopyralid stress: a comparative analysis of nitrogen removal performance and microbial community structure - Chi Sun; Yi Han; Jianbing Zhang; Haibo Li; Runnan Zhao (Bioresource Technology Reports, 2026)

The jamming and spoofing of GNSS in Persian Gulf during the Israel-Iran conflict: an analysis by receiver data - Da Xu; Hongqing Li; Yongchun Wang; Dong Huang; Han Zhao; Jiageng Chi; Qiong Wu (Advances in Space Research, 2026)

Pharmacokinetics and Withdrawal Time of Doxycycline in Snakehead ( Channa striata ) Following Oral Medication - Nguyen Quoc Thinh; Han Chi Thien; Mathias Devreese; Siska Croubels; Masashi Maita; Tran Minh Phu (Journal of Fish Diseases, 2026)
The study consisted of two experiments. First, a PK experiment was set up with a single oral dose at 20 mg/kg body weight, and second, a withdrawal time determination study, where the fish were fed once a day for 5 consecutive days at the same dosage. The DOX concentration in medicated feed, fish muscle, plasma, liver, and kidney was analysed by LC–MS/MS. Phoenix 8.1 and WT 1.4 software were used in the calculation for PK parameters and withdrawal time, respectively. DOX was absorbed quickly into plasma after oral medication with an absorption half‐life T 1/2abs of 0.12 h, reaching the C max (116 μg/L) at 1 h ( T max ). DOX distribution was highest in the kidney, followed by the liver and plasma. The high DOX concentration in the kidney and liver supports the possibility of using DOX to treat relevant bacterial infections in snakehead. In conclusion, DOX is rapidly absorbed in snakehead after oral medication, has a significant tissue distribution, followed by slow elimination. Finally, after feeding medicated feed for 5 consecutive days, the withdrawal times of DOX in composite muscle and skin samples of snakehead were 4 days and 6 days (at 28.5°C) according to the maximum residue limits set by the European Commission (100 μg/kg for bovine, porcine and poultry) and Japanese authority (50 μg/kg), respectively.

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Design of key components for a low-loss air-blowing sesame harvest header and study on material transport mechanisms based on CFD simulation - Han Tang; Zhiyuan Sun; Fudong Xu; Chi Zhang; Qi Wang; Jinwu Wang (Computers and Electronics in Agriculture, 2026)

Fine-scale aboveground biomass estimation of restored vegetation in tailings ponds: integrating UAV multi-source data and explainable machine learning - Xiaojie Chi; Mingming Jia; Jingjing Zhao; Fuping Li; Chunyan Lu; Yongbin Zhang; Dongyun Han; Xiaohui Hu; Xiaoguang Li; Guie Tian; Mingyue Liu; Weidong Man (Computers and Electronics in Agriculture, 2026)

Luteolin-stabilized pickering emulsion for encapsulating Enterococcus hirae: preparation, characterization, and synergistic effects on hyperuricemia - Chengtao Han; Songhao Che; Hui-Min Li; Yan-Yu Chi; Jun-Yan Xiang; Qiuhong Xie; Hongyu Xiang (Food Research International, 2026)

Synergistic catalytic mechanism of constituent metal atoms in high−entropy alloy catalysts for Li − S batteries - Tong Qi; Yu Shao; Chi Zhang; Di Wang; Fengfeng Han; Qi Jin; Zhihao Liu; Xitian Zhang; Lu Li; Lili Wu (Chemical Engineering Journal, 2026)

N-acetylcysteine-functionalized biodegradable polysaccharide hydrogel patches for the repair of acute liver injury - Shanshan Li; Lixin Xia; Shuo Wang; Ruibao Ju; Zi Han; Xiansen Lv; Baoqin Han; Jinhua Chi (Carbohydrate Polymers, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Machine Learning Approaches for Probabilistic Prediction of Coastal Freak Waves - Dong-Jiing Doong; Wei-Cheng Chen; Fan-Ju Lin; Chi Pan; Cheng-Han Tsai (Journal of Marine Science and Engineering, 2026)
Coastal freak waves (CFWs) are sudden and hazardous wave events that occur near shorelines and can pose serious threats to coastal visitors and infrastructure. Due to the complex interactions among coastal bathymetry, wave dynamics, and environmental conditions, the mechanisms governing CFW formation remain poorly understood, making reliable prediction difficult. This study investigates the feasibility of applying machine learning techniques to predict CFW occurrences using observational environmental data. Three machine learning algorithms, the Random Forest (RF), Support Vector Machine (SVM), and Artificial Neural Network (ANN), were developed to generate probability-based predictions of CFW events. Environmental variables derived from buoy observations, including wave characteristics, wind conditions, swell parameters, wave grouping indicators, and nonlinear wave interaction indices, were used as model inputs. Hyperparameters were optimized using grid search combined with k-fold cross-validation. The results show that all three models achieved comparable predictive performance, with AUC values close to 0.80 and overall prediction accuracy around 74%. The ANN model achieved the highest recall, indicating strong capability in detecting CFW events, while the RF and SVM models showed more balanced precision and recall. Analysis of high-probability prediction events suggests that CFW occurrences are associated with swell-dominated conditions, strong wave grouping behavior, and enhanced nonlinear wave interactions. These results demonstrate that machine learning provides a promising framework for probabilistic prediction of coastal freak waves and has potential applications in coastal hazard assessment and early warning systems.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Biomimetic fabrication of cultured meat using 3D-printed microgrooved and meshed scaffolds with alternating muscle and adipose layers - Chi-Han Li; Chih-Ying Chi; Feng-Huei Lin; Chia-Ting Chang; I-Hsuan Yang (Food Hydrocolloids, 2026)

Differential robustness of microalgal-bacterial biofilm to once and consecutively changing multi-stressors: Combined impacts of salinity, nutrients, and hydrodynamic loads - Yang Liu; Yi-Ran Zhai; Xiang-Yi Kong; Jing-Han Wang; Zhan-You Chi; Jian-Gang Ren (Bioresource Technology, 2026)

Uncovering hidden VOCs risks in metro halls: A non-targeted screening and health risk during extreme summer heatwaves - Han Wang; Jiyue Wang; Guangming Li; Youyan Chi; Mengsi Deng; Kwok Wai Tham; Chunhui Li (Building and Environment, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Cover crop incorporation with moderate nitrogen reduction regulates soil microbial communities to drive C:N stoichiometry for enhanced peanut yield and efficiency - Lijun Chi; Yatong Chu; Han Zeng; Xinran Guo; Xiuzhi Zang; Tianxiao Cao; Jin Chen; Kun Zhang; Dongqing Yang (Field Crops Research, 2026)

Unlocking potassium sustainability: Rice-crab co-culture system enhances potassium balance - Haixia Liu; Xuran Liu; Feng Zhang; Hongwei Han; Yinghao Li; XiaoLi Wu; Guangyan Liu; Daocai Chi; Jun Meng; Taotao Chen (Field Crops Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Structural and orbital multifunctional intercalation engineering of vanadium oxide for aqueous zinc-ion storage - Zi-Hang Huang; Liwen Yang; Fang-Fang Sun; Yue Zhang; Bing Tang; Fanglin Liao; Miao Liu; Ji-Chi Liu; Hui Li; Xu Han; Tianyi Ma (Chemical Engineering Journal, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Sustainable synthesis of polycarbonate-based non-isocyanate polyurethane via double metal cyanide catalysis - Chinh Hoang Tran; Han Su Lee; Ngoc Thanh Truong; Phuong Ngoc Nguyen; Nghiem Anh Tuan Le; Duy Du Bui; Chi Le Hoang Tran; Khoa Anh Trinh; Giang Ngoc Doan; Van Du Cao; Il Kim (Journal of Environmental Chemical Engineering, 2026)

Optimizing fertilizer and planting density to stabilize yields and improve water use efficiency in rain-fed wheat–maize rotations - Xueni Yang; Shujie Sun; Haocong Li; Ziyan Guo; Chi Ma; Bo Liu; Wei Zhang; Ruixia Ding; Peng Zhang; Tiening Liu; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2026)

In-situ fabrication of magnetic prussian blue composites for highly selective rubidium recovery from high-salinity brine - Zheng Li; Zilong Chen; Chi Ma; Wei Qin; Jiantuan Jia; Guang Han; Yafei Guo; Tong Pan; Tianlong Deng (Desalination, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Facet-engineered epitaxial TiO2 for early hydrogen detection in lithium-ion battery thermal runaway - Yuanyuan Fu; Liuxi Chen; Weifang Ma; Kaixin Wang; Hanwen Chi; Ni Tu; Jianing Mao; Yunna Guo; Liqiang Zhang; Zhizhen Ye; Zhong-kang Han; Qiyan Wang; et al. (Chemical Engineering Journal, 2026)

The first complete mitochondrial genome characterization of Lutjanus fulvus (Perciformes: Lutjanidae) and phylogenetic analysis within the Lutjanidae family - Luxiu Gao; Yifan Liu; Faiz Muhammad; Taobo Feng; Mingzhe Han; Chi Zhang; Bingjian Liu (Zoologischer Anzeiger, 2026)

Effect of tamping on mechanical response in sandy ballast bed based on microscopic sand profile reconstruction and DEM - Zhihai Zhang; Hong Xiao; Dong Ding; Han Wang; Yihao Chi; Yang Wang; Huan Wang (Transportation Geotechnics, 2026)

Visual toxicity of imidacloprid in zebrafish: Unraveling the pathways from ocular morphology to behavior via phototransduction dysregulation - Ruiqiang Fu; Hanfei Zheng; Han Gao; Liangang Mao; Chi Wu; Lizhen Zhu; Xingang Liu; Lan Zhang (Journal of Hazardous Materials, 2026)

Does the farmers’ social learning matter? Unveiling the behavioral motivation for adopting agricultural green production - Lexuan Huang; Han Meng; Zhengjia Zhang; Xiangyang Zhou; Liang Chi; Mengshuai Zhu; Jianzhai Wu (Journal of Cleaner Production, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Ultrasound-sensitized gas vesicles enable spatiotemporal therapeutics of solid tumors - Juanjuan Li; Yong Liu; Xiaoli Jiang; Jiani Han; Yanqiong Tang; Hong Li; Xiang Ma; Xue Chi; Min Lin; Zhu Liu (Chemical Engineering Journal, 2026)

Late Pliocene-Quaternary climate-environment evolution on the southeastern Tibetan Plateau and links to hominin dynamics - Yidan Long; Wenxia Han; Boyan Sun; Yifei Fan; Xue Xiao; Tianli Wang; David B. Kemp; Chenyu Shang; Yunping Chi; Xiaomin Fang (CATENA, 2026)

Top-down selection of pit mud local microbial community for efficient anaerobic digestion of distilled grain waste - Tao Xu; Mengya Han; Yan Zeng; Rujie Yang; Ling Xiang; Hanlan Tang; Xiaotong Liu; Yuanlong Chi; Zhenghong Xu; Suyi Zhang; Danqun Huo; Xiaozhong Zhong (Bioresource Technology, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

PRINCE: Advanced classification algorithm for rice grain recognition in clustered images - Bidong Chen; Lingui Li; Han Zhu; Meijuan Tan; Guanhua Liu; Haiyang Chi; Xu Yang; Yapeng Wang (Computers and Electronics in Agriculture, 2025)

Semi-continuously operated single strain microalgal-bacterial biofilm for nutrients removal: microbial succession and performance improvement over extended non-axenic operation - Jing-Tian Zhang; Tong Wu; Jian-Xia Wang; Yang Liu; Jing-Han Wang; Zhan-You Chi; Jian-Gang Ren (Water Research, 2025)

Research on cracking behavior of ice specimens containing single and double flaws under uniaxial compression - Chen Chi; Yiheng Zhang; Ying Tang; Xiaobin Li; Wei Chen; Qing Wang; Duanfeng Han; Yinggang Li (Ocean Engineering, 2025)

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

Computational toxicology Insights into pyriproxyfen and its transformation products: An overlooked driver of aquatic toxicity and endocrine disruption - Min Li; Lang Chen; Han Gao; Leyuan Ji; Feng Chen; Lan Zhang; Liangang Mao; Lizhen Zhu; Xingang Liu; Chi Wu (Journal of Environmental Management, 2025)

Thermophilic composting of dewatered sewage sludge under subzero temperatures using a full-scale pre-fermentation reactor: A 10-day valorisation strategy for year-round operation - Huitae Min; Hyejin Ko; Sang Hoon Jung; Ji Yeon Han; Chi Won Lee; Seungchan An; Young-Joo Kim; Taejung Kim; Jungyeob Ham; Wonbae Kim; Young-Tae Park (Journal of Environmental Management, 2025)

Stereoselectivity during enzymatic oxidation of catechins and their products' characteristic in taste receptors and color properties - Zekai Wang; Qing-Qing Cao; Mingchun Wen; Yahui Li; Yuqing Cui; Zisheng Han; Xiaochun Wan; Chi-Tang Ho; Yong-Quan Xu; Liang Zhang (Food Chemistry, 2025)

Rice-crab coculture produces higher carbon sink and eco-economic benefits - Hongwei Han; Taotao Chen; Feng Zhang; Haixia Liu; Yikui Bai; Daocai Chi (Field Crops Research, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Semantic Consistency Network with Edge Learner and Connectivity Enhancer for Cervical Tumor Segmentation from Histopathology Images - Lisha Pang; Peng He; Yue Han; Hao Cui; Peng Feng; Chi Zhang; Pan Huang; Sukun Tian (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Corrigendum to “Assessing CO₂ sources and sinks in and around Taiwan: Implication for achieving regional carbon neutrality by 2050” [Mar. Pollut. Bull. 206 (2024) 116664]. - Chin-Chang Hung; Hsueh-Han Hsieh; Wen-Chen Chou; En-Chi Liu; Chun Hoe Chow; Yi Chang; Tse-Min Lee; Peter Hans Santsch; R.R.M.K.P. Ranatunga; Hernando P. Bacosa; Yung-Yen Shih (Marine Pollution Bulletin, 2025)

Promoted chlorobenzene deep oxidation over CeCo10Ox-P nanosheet catalyst via acid site and oxygen vacancy rational construction - Yahao Wang; Mingjiao Tian; Yaruo Zhao; Han Xu; Dong Guo; Jiaxun Zhang; Zeyu Jiang; Qin Yang; Lu Li; Chi He (Chemical Engineering Journal, 2025)

Spherical LTA zeolite/poly(acrylates) composite with hierarchical pores for high-efficiency CO2 capture - Shudan Chi; He Wen; Wei Han; Kun Liu; Junsu Jin; Yongqiang Ren; Jianguo Mi; Shisen Xu (Chemical Engineering Journal, 2025)

In-situ polyimidazole-encapsulated Cu-defective PB composite enables green and selective rubidium recovery from salt lake brine - Chi Ma; Zheng Li; Zhongjing Zhang; Wei Qin; Jiantuan Jia; Guang Han; Yafei Guo; Tong Pan; Tianlong Deng (Chemical Engineering Journal, 2025)

Self-powered humidity sensor based on porous Ti₃C₂Tₓ MXene: High sensitivity and fast response for real-world applications - Linh Chi T. Cao; Luqman Hakim; Yuki Nagao; Sakoolkan Boonruang; Shih-Feng Tseng; Shu-Han Hsu (Chemical Engineering Journal, 2025)

Secondary metabolites from marine-derived fungus Aspergillus sp. SF6390 and their biological effects - Chi-Su Yoon; Fangfei Tang; Joung Han Yim; Il-Chan Kim; Jae Hak Sohn; Dong-Sung Lee; Haeun Kwon; Dongho Lee; Hyuncheol Oh (Natural Product Research, 2025)

Downstream impacts of the land-surface thermal anomalies over West Asia on synoptic-time-scale atmospheric variability - Yang Zhou; Boyang Lei; Pang-Chi Hsu; Lei Han; Shanlei Sun; Mengke La; Haishan Chen (Climate Dynamics, 2025)

Modified two-dose difference with stable isotope tracing workflow using mass shift defect filtering substantially reduces false positives in untargeted nifedipine metabolite profiling - Sheu-Fang Lo; Yi-Shiou Chiou; Jie-Huei Wang; Zih-Han Wu; Meng-Chi Yen; Chia-Lung Shih (Analytica Chimica Acta, 2025)

The ternary synergy of Fe, N and P enhances the membrane capacitive deionization performance of porous biochar - Houqi Zhou; Ting Xu; Chi Fei; Yilong Fan; Keying Tang; Chunyu Chen; Dianchun Ju; Han Ma; Zuoqiao Zhu; Rui Mao (Journal of Environmental Chemical Engineering, 2025)

Discovery and identification of novel color compound formed from EGCG upon heating: Integrated multispectral, sensory evaluation, metabolomics, and nuclear magnetic resonance - Zongde Jiang; Zixin Zhao; Zisheng Han; Jiaping Ke; Chunyin Qin; Chi-Tang Ho; Xiaoting Zhai; Yijun Wang; Liang Zhang; Xiaochun Wan (Food Chemistry, 2025)

Co-existence of normal and lognormal distributions for climate and environmental parameters in air-conditioned spaces - Wei Jia; Han Xiao; Wai-hung Leung; Ka Long Yick; Ka Fai Se-To; Chi Kong Fok; Pak Wai Chan; Yuguo Li (Energy and Buildings, 2025)

Superior charge dynamics via ternary doping layer-by-layer strategy in high-efficiency organic solar cells - Chao Zhang; Shixiu Sun; Tengfei Han; Jie Chi; Ran Dong; Shulin Han; Hang Zhou; Yujie Xu; Lei Cai; Xiaoyan Du; Sang Young Jeong; Han Young Woo; et al. (Chemical Engineering Journal, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Nitrogen utilization in response to cadmium and abscisic acid in rice - Zhi-Jun Xu; Jia-Yi Qu; Meng Zhao; Jing Zhao; Wei-Chi Wang; Jia-Jun Huang; Jia-Shi Peng; Yun-Hua Xiao; Yong-Liang Han; Yan Peng; Bo-Han Liu; Zhen-Xie Yi; et al. (Plant and Soil, 2025)

Improving dynamical downscaling simulations of western North Pacific tropical cyclones using bias-corrected CMIP6 data - Ying Han; Zhongfeng Xu; Meng-Zhuo Zhang; Chi-Yung Tam; Vincent S. Cheng; Hon-man Wong; Xiaofeng He; Yi Wang; Si-nan Gu (Climate Dynamics, 2025)

Reanalysis-data-based approach to generate urban local weather data to support building energy design in a tropical climate - Xing Zheng; Naika Meili; Shuyang Li; Huanhuan Wang; Lei Xu; Zhen Han; Martín Mosteiro-Romero; Yi Wu; Da Yan; Dengkai Chi; Guanli Feng; Rudi Stouffs (Sustainable Cities and Society, 2025)

Application of spectral induced polarization technique in monitoring zinc removal by activated carbon as a permeable reactive barrier material - Sheng Zhou; Yi-Xin Yang; Jing-Jing Cao; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Contaminant Hydrology, 2025)

Adaptive fertilization strategies for premature senescence challenges in film-mulched maize: Insights from a 4-year field study - Haixiang Xiong; Chi Ma; Shujie Sun; Ziyi Wang; Ji Zhao; Chun Zhang; Lin Yang; Zhaoyun Dong; Zhikuan Jia; Dan Liu; Qingfang Han; Xudong Zhang (European Journal of Agronomy, 2025)

Porosity-controlled MXene anodes for enhanced rate and long cycle life performance in aqueous proton batteries - Linh Chi T. Cao; Kentaro Aoki; Shu-Han Hsu; Sakoolkan Boonruang; Yuki Nagao (Chemical Engineering Journal, 2025)

Corrigendum to “Effects of carboxymethyl chitosan oligosaccharide on regulating immunologic function and inhibiting tumor growth” [Carbohydrate Polymers 250 (2020) 116994] - Zhiwen Jiang; Shuning Wang; Jun Hou; Jinhua Chi; Shuo Wang; Kai Shao; Wanshun Liu; Rongju Sun; Baoqin Han (Carbohydrate Polymers, 2025)

Seasonal variation and health risks of rural indoor PAHs in severely cold regions: Effects of heating type and energy structure - Chunhui Li; Han Wang; Youyan Chi; Kwok Wai Tham; Li Bai; Zhenhai Li (Building and Environment, 2025)

Exploring the potential of Trichoderma asperellum TCS007 on growth promotion of pecan seedlings as well as rhizosphere soil nutrients and microbial community - Hao Cao; Xue-song Li; Hao Han; Sai Chen; Jing Jin; Jing Yuan; Chi-zhou Liang; Jian-fei Lu; Feng Cui; Jie Chen (Plant and Soil, 2025)

Effect of the 5-HT7Ar gene on the reproductive performance of parthenogenetic Artemia - Rui Zhang; Xuemei Ouyang; Ke Li; Chi Zhang; Liangsen Liu; Liying Sui; Xuekai Han (Journal of Oceanology and Limnology, 2025)

Halomonas sp. NEC-1, an ectoine-rich and wide pH tolerant halophilic bacterium isolated from a salt lake of Xizang, China - Yingchao Ma; Zhongshi Sun; Tashilhamo; Yukang Li; Hanying Zou; Yuanliang Zhao; Feiyang Lin; Xuekai Han; Liying Sui; Chi Zhang (Journal of Oceanology and Limnology, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Biaxially oriented polyethylene (BOPE) and exogenous H2S extend strawberry shelf-life by increasing antioxidant activity and inhibiting pigment accumulation - Ying-Chun Song; Yu-Qi Zhao; Chi-Ming Tang; Pedro Garcia-Caparros; Si-Yu Yang; Jia-Qi Yu; Xiu-Ting Hu; Kang-Di Hu; Zhuo Han; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Geochemical remediation and spectral induced polarization monitoring of Cu2+ by geographically abundant paleosol and loess - Yi-Xin Yang; Sheng Zhou; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Water Process Engineering, 2025)

Seawater intrusion causes substantial release of dissolved organic carbon in coastal paddy soils - Wenting Chi; Yang Yang; Pei Wang; Chao Guo; Zebin Hong; Shiwen Hu; Kuan Cheng; Shan Wang; Han Li; Qi Wang; Ying Li; Yang Wu; et al. (Geochimica et Cosmochimica Acta, 2025)

Seafloor thermal structures controlled by recent slope failure and fluid flow: An example from offshore SW Taiwan - Wei-Chung Han; Liwen Chen; Wu-Cheng Chi; Hsieh-Tang Chiang; Song-Chuen Chen; Char-Shine Liu; Chuen-Tien Shyu (Marine and Petroleum Geology, 2025)

Calling out for studying microplastics at environmentally relevant conditions: aquatic distribution, differential impacts on microalgae by aged and pristine microplastics, and mechanisms of altered toxicity - Ming-Zhi Shen; Liu Yang; Jing-Han Wang; Zhan-You Chi; Qiang Zhang (Journal of Cleaner Production, 2025)

Dual role of exogenous xylose in regulating pyrazines and furans formation during the thermal degradation of N,N-di(1-deoxy-d-xylulos-1-yl)lysine through temperature, reaction time, and xylose concentration control - Han Zhang; Heping Cui; Xue Xia; Shahzad Hussain; Khizar Hayat; Xiaoming Zhang; Chi-Tang Ho (Food Chemistry, 2025)

Microalgal-bacterial system responses to nitrogen forms in dairy farm wastewater: Focusing on the phycosphere and nitrogen transformation - Yuang Cao; Xiaoyu Xu; Suli Zhi; Khinkhin Phyu; Han Wang; Jiahua Liu; Chein-Chi Chang; Keqiang Zhang (Environmental Research, 2025)

Crystallization-driven effect enables organic solar cells with efficiency exceeding 19.4 % - Tengfei Han; Jie Chi; Ran Dong; ShuLin Han; Hang Zhou; Yujie Xu; Byung Hui Lee; Lei Cai; Xiaoyan Du; Han Young Woo; Fujun Zhang; Chao Zhang; et al. (Chemical Engineering Journal, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Hazardous VOCs pollution and health effects in metro carriages in different building climate zones: A comparative study in China - Chunhui Li; Han Wang; Guangming Li; Youyan Chi; Li Bai; Zhenhai Li; Kwok Wai Tham (Building and Environment, 2025)

Recent Advances in Three-Dimensional In Vitro Models for Studies of Liver Fibrosis - Kyun Yoo Chi; Gyeongmin Kim; Jeong Sang Son; Jiyou Han; Jong-Hoon Kim (Tissue Engineering and Regenerative Medicine, 2025)

LINE-1 DNA methylation mediates smoking-related risk in site-specific urothelial carcinoma: a Taiwan case–control study - Chien-Hung Lin; Peir-Haur Hung; Chao-Hsiang Chang; Han Chang; Mu-Chi Chung; Wen-Chi Chang; Chi-Jung Chung (Archives of Toxicology, 2025)

Mapping of paddy field by Sentinel-1 SAR images and cadastre data in Yunlin, Taiwan - Jui-Han Yang; Kuo-Hsin Tseng; Shu-Ling Chen; Ya-Lun Tsai; Ray. Y. Chuang; Aive Liibusk; Chi-Farn Chen (International Journal of Remote Sensing, 2025)

Establishment of carrier enhanced microalgal granules and their stability in municipal wastewater treatment under various hydraulic and solid retention times - Jian-Xia Wang; Su-Liang Liu; Xiang-Yi Kong; Jing-Han Wang; Zhan-You Chi (Journal of Water Process Engineering, 2025)

Establishing microalgal-bacterial biofilm for estuary remediation and the impacts of salinity, nutrients, and hydrodynamic loads on biofilm performances - Yang Liu; Ao Zhang; Tong Wu; Jing-Han Wang; Zhan-You Chi (Journal of Environmental Chemical Engineering, 2025)

Numerical simulation of GPR via Leapfrog ADI-FDTD - Bohua Wang; Hongyan Shen; Han Che; Shuai Liu; Chi Wang; Chengwei Zhang; Hao Wang; Shisheng Feng; Kanglong Wang (Journal of Applied Geophysics, 2025)

Impact of dispersion correction in DFT-enhanced anisotropic NMR for stereochemical elucidation of flexible marine natural products - Lu-Ping Chi; Xiao-Lu Li; Anton F. Ketzel; Armando Navarro-Vázquez; Caspar J. Schattenberg; Xiao-Ming Li; Xin Li; Han Sun; Bin-Gui Wang (Marine Life Science & Technology, 2025)
Although anisotropic NMR spectroscopy has emerged as a powerful method for determining the relative configuration of complex natural products, major challenges persist with structurally flexible molecules. In this study, we conducted a systematic comparative analysis of stereochemical elucidation, combining anisotropic NMR spectroscopy and density functional theory (DFT) calculations on spiroepicoccin B ( 1 ) and epicoccin V ( 2 ), which were characterized as thiodiketopiperazine marine natural products isolated from the deep-sea-derived fungus Epicoccum nigrum SD-388. For the flexible compound 2 , we compared various conformational sampling approaches, including an assessment of the quality of relative energies within the obtained ensembles. We demonstrated the critical role of dispersion correction within DFT computations to precisely account for weak non-bonded intramolecular interactions. By integrating anisotropic NMR analysis, chemical shifts, electronic circular dichroism, and DFT computations, we determined the absolute configurations and conformational ensembles for 1 and 2 , respectively, highlighting the significance of the intramolecular methyl–π interaction in stabilizing one of the conformers. Our study introduces new strategies to address conformational flexibility in the stereochemical elucidation of challenging organic molecules.

An Ocular Exposure Prediction for Topical Atropine in Human Using Physiologically Based Pharmacokinetic Modeling - Aole Zheng; Tian Han; Fengjiao Bu; Qingfeng He; Jianmin Shang; Paul Chi Lui Ho; Xiaoqiang Xiang; Xingtao Zhou; Taomin Huang (The AAPS Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Less toxic combined microplastics exposure towards attached Chlorella sorokiniana in the presence of sulfamethoxazole while massive microalgal nitrous oxide emission under multiple stresses - Ying Zhang; Ming-Zhi Shen; Jian-Xia Wang; Jing-Han Wang; Zhan-You Chi (Journal of Hazardous Materials, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Evaluating the influence of topography data resolution on lake hydrodynamic model under a simulation uncertainty analysis framework - Quan Han; Ling Zhou; Wenchao Sun; Jinqiang Wang; Chi Ma (Environmental Modelling & Software, 2025)

Unveiling the role of heteroatom doping and strain in Core-Shell catalysts for CO2RR - Yiran Bai; Yunjian Wang; Yibing Yang; Chen Sun; Hsiao-Tsu Wang; Chi-Feng Lee; Cheng-You Li; Tingting Zheng; Kunpeng Jiang; Lili Han (Chemical Engineering Journal, 2025)

Anti-inflammatory and antioxidant succinyl-chitosan oligosaccharide protects human epidermal cell and mouse skin against ultraviolet B-induced photodamage - Xiansen Lv; Zi Han; Huilin Huo; Xiaofei Liu; Jinpeng Zhang; Jinhua Chi; Baoqin Han; Zhiwen Jiang (Carbohydrate Polymers, 2025)

Effects of stratified microbial extracellular polymeric substances on microalgae dominant biofilm formation and nutrients turnover under batch and semi-continuous operation - Jing-Tian Zhang; Jian-Xia Wang; Yang Liu; Jing-Han Wang; Zhan-You Chi (Bioresource Technology, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Inversion of Rayleigh wave dispersion curves integrating the Osprey–Cauchy and Pigeon-inspired optimization algorithm - Shuai Liu; Hongyan Shen; Han Che; Bohua Wang; Chi Wang; Chengwei Zhang; Guangzhou Shao; Shisheng Feng; Hao Wang; Kanglong Wang (Acta Geophysica, 2025)

Zeolite mitigates alternate wetting and drying – Induced potassium depletion and enhances potassium balance in rice paddies: A 6-year field study - Hongwei Han; Taotao Chen; Yongchao Su; Shu Zhang; Qing Zhao; Yidi Sun; Yikui Bai; Daocai Chi (Field Crops Research, 2025)

Facile manufacturing solutions for ultra-durable flexible MXene micro-supercapacitors in 8-inch scale - Eunji Kim; Yunhui Choi; Hyeong Jin Kim; Hyeong Min Jin; Yeon-Wha Oh; Sanghee Jung; Il-Suk Kang; Hee Han; Jaewoo Roh; Il-Kwon Oh; Jinwoo Lee; Chi Won Ahn; et al. (Chemical Engineering Journal, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Coupling phylogenetic relatedness and distribution patterns provides insights into sandburs invasion risk assessment - Ming Yang; Yuhan Qi; Xiaoqing Xian; Nianwan Yang; Lin Xue; Chi Zhang; Han Bao; Wanxue Liu (Science of The Total Environment, 2025)

Interaction of Ca2+ and Fe3+ in co-precipitation process induced by Virgibacillus dokdonensis and its application - Huaxiao Yan; Yuping Liu; Haojuan Zhang; Shengping Jin; Zuozhen Han; Jusun Woo; Maurice E. Tucker; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Yueming Zhao; et al. (Journal of Environmental Sciences, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Study on pilot-scale inline jet flow high shear mixer: Discharge, macro-mixing time, and residence time distribution - Junbo Wu; Junheng Guo; Yudong Liu; Kangkang Ma; Yingcheng Wang; Wei Li; You Han; Ruan Chi; Bingwen Long; Jinli Zhang (Chemical Engineering Journal, 2025)

Microalgae create a highway for carbon sequestration in livestock wastewater: Carbon sequestration capacity, sequestration mechanisms, influencing factors, and prospects - Han Wang; Jiahua Liu; Khinkhin Phyu; Yu'ang Cao; Xiaoyu Xu; Junfeng Liang; Chein-Chi Chang; Keqiang Zhang; Suli Zhi (Science of The Total Environment, 2024)

Legacy sources determine current water quality: Nitrogen and phosphorus in streams of Australia, China, Sweden and USA - Jianxu Han; Georgia Destouni; Jerker Jarsjö; Qin Zhang; Jacopo Cantoni; Chi Zhang (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Integration of multiple observations for validation of mechanisms of earthquake-triggered groundwater level Anomalies: 2016 Taiwan Meinong earthquake - Shih-Jung Wang; Yan-Yao Lin; Ying-Han Chen; Chia-Lin Chung; Wen-Chi Lai; Chien-Chung Ke (Journal of Hydrology, 2024)

Investigating spatial-temporal trend of snow cover over the three provinces of Northeast China based on a cloud-free MODIS snow cover product - Zhao Gao; Zhihong Liu; Pengfei Han; Chi Zhang (Journal of Hydrology, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Highly efficient and sustainable polyacrylic acid-polyacrylamide double-network hydrogels prepared by cross-linking of waste residues for heavy metals ions removal - Mengyu Ma; Yingying Li; Danni Wang; Jia Li; Hengpeng Ye; Dongyun Du; Ruan Chi; Qingwen Han (Journal of Environmental Chemical Engineering, 2024)

Identification and quantification of unreported sialylated N-glycan isomers with α2-3 and α2-6 linkages in the egg yolk protein phosvitin - Subin Yang; Chang Myeong Jeong; Chi Soo Park; Chulmin Moon; Leeseul Jang; Ji Yeon Jang; Han Seul Lee; Kyuran Kim; Haeun Byeon; Daeun Eom; Ha Hyung Kim (Food Research International, 2024)

Crocin-1 laden thermosensitive chitosan-based hydrogel with smart anti-inflammatory performance for severe full-thickness burn wound therapeutics - Xiansen Lv; Hui Li; Ya Chen; Yanting Wang; Jinhua Chi; Shuo Wang; Yan Yang; Baoqin Han; Zhiwen Jiang (Carbohydrate Polymers, 2024)

Organic carbon decomposition temperature sensitivity positively correlates with the relative abundance of copiotrophic microbial taxa in cropland soils - Yuan Du; Anlan Yu; Yuan Chi; Zelin Wang; Xinrui Han; Kaifang Liu; Qiuping Fan; Xin Hu; Rongxiao Che; Dong Liu (Applied Soil Ecology, 2024)

Stimulating innovation or enhancing productivity? The impact of environmental regulations on agricultural green growth - Lexuan Huang; Xiangyang Zhou; Liang Chi; Han Meng; Guodong Chen; Chen Shen; Jianzhai Wu (Journal of Environmental Management, 2024)

Preparation and functional characterization of pullulan-sodium alginate composite film enhanced with ultrasound-assisted clove essential oil Nanoemulsions for effective preservation of cherries and mushrooms - Arif Rashid; Abdul Qayum; Syed Asim Shah Bacha; Qiufang Liang; Yuxuan Liu; Lixin Kang; Zhuzhong Chi; Runhao Chi; Xu Han; John-Nelson Ekumah; Muhammad Safi Ullah Virk; Xiaofeng Ren; et al. (Food Chemistry, 2024)

Novel pullulan-sodium alginate film incorporated with anthocyanin-loaded casein-carboxy methyl cellulose nanocomplex for real-time fish and shrimp freshness monitoring - Arif Rashid; Abdul Qayum; Syed Asim Shah Bacha; Qiufang Liang; Yuxuan Liu; Lixin Kang; Zhuzhong Chi; Runhao Chi; Xu Han; John-Nelson Ekumah; Muhammad Safiullah Virk; Xiaofeng Ren; et al. (Food Hydrocolloids, 2024)

Experimental study on migration and transformation of inorganic components during purification-combustion - Yujie Hu; Wei Li; Shaobo Yang; Shaobo Han; Ruifang Cui; Chi Zhang; Qiangqiang Ren (Chemical Engineering Journal, 2024)

Integrative analysis of nutrient dynamics and its hydrological pathways in a tropical montane forest watershed: Implications for landscape management - Pengtao Wang; Dongyang Han; Chi Zhang; Fei Yu; Xin Wang; Pengfei Huang; Ganggang Zhang; Shaoqing Liu (CATENA, 2024)

Exploring the effects of pemetrexed on drug resistance mechanisms in human lung adenocarcinoma and its association with PGRMC1 - Ssu-Yun Wu; En-Chi Liao; Yueh-Feng Wen; Yi-Shiuan Wang; Han Meng; Hsiu-Chuan Chou; Hong-Lin Chan (Chemico-Biological Interactions, 2024)

Design, synthesis and biological evaluation of novel pyrimidine-phenylsulfonylfuroxan hybrids - Dongling Gu; Shihao Wang; Zichen Yang; Hongjing Chen; Jiahui Han; Lingling Chi; Fuqiang Yu; Hao Wang; Jiaxin Zheng; Peirong Zhao; Hongmin Liu; Yu Ke; et al. (Medicinal Chemistry Research, 2024)

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

The long-term nitrogen fertilizer management strategy based on straw return can improve the productivity of wheat-maize rotation system and reduce carbon emissions by increasing soil carbon and nitrogen sequestration - Ziyan Guo; Yang Liu; Xiangping Meng; Xueni Yang; Chi Ma; Huina Chai; Hui Li; Ruixia Ding; Khudayberdi Nazarov; Xudong Zhang; Qingfang Han (Field Crops Research, 2024)

Probabilistic evaluation method for the stability of large underground cavern considering the uncertainty of rock mass mechanical parameters: A case study of Baihetan underground powerhouse project - Guofeng Liu; Chi Zhou; Kun Feng; Quan Jiang; Shengfeng Li; Han Bao; Ang Li (Engineering Geology, 2024)

Mixed microalgal culture enhances biofilm adhesion during treatment of livestock wastewater: The role of extracellular polymeric substances - Jiahua Liu; Zengjun Yang; Khinkhin Phyu; Yu’ang Cao; Han Wang; Xiaoyu Xu; Junfeng Liang; Keqiang Zhang; Chein-Chi Chang; Suli Zhi (Chemical Engineering Journal, 2024)

Mechanism of chloride modification ambipolar polymer electrode materials for high-performance energy storage device - Weiwei Hou; Dianyu Tang; Bingbing Han; Yusheng Chen; Chenze Wang; Yihu Liu; Wentao Chi; Junhong Chen; Yicheng Zhu; Mi Ouyang; Junlei Liu; Cheng Zhang (Chemical Engineering Journal, 2024)

Capsaicin reduces blood glucose and prevents prostate growth by regulating androgen, RAGE/IGF-1/Akt, TGF-β/Smad signalling pathway and reversing epithelial-mesenchymal transition in streptozotocin-induced diabetic mice - Hui Sun; ZiTong Wang; BingHua Tu; ZiChen Shao; YiDan Li; Di Han; YinJie Jiang; Peng Zhang; WeiChang Zhang; YunYan Wu; XiaoMing Wu; Chi-Ming Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Dual-porous ZIF-8 heterogeneous catalysts with increased reaction sites for efficient PET glycolysis - Nara Han; Kyunghan Lee; Jieun Lee; Jin Hui Jo; Eun Ji An; Gicheon Lee; Won Seok Chi; Chanmin Lee (Chemosphere, 2024)

Assessing CO2 sources and sinks in and around Taiwan: Implication for achieving regional carbon neutrality by 2050 - Chin-Chang Hung; Hsueh-Han Hsieh; Wen-Chen Chou; En-Chi Liu; Chun Hoe Chow; Yi Chang; Tse-Min Lee; Peter Hans Santschi; R.R.M.K.P. Ranatunga; Hernando P. Bacosa; Yung-Yen Shih (Marine Pollution Bulletin, 2024)

Trophic ecology of the greater amberjack in relation to marine environmental characteristics in Taiwanese waters illustrated by stable isotope and stomach content approach - Mubarak Mammel; Pokkathappada Abdul Azeez; Yi-Chen Wang; Yang-Chi Lan; Han-Yang Yeh (Regional Studies in Marine Science, 2024)

Release of high-pressure hydrogen from type III tank in a fire scenario: Analysis and prediction of jet flame length and thermal response characteristics - Linzhi Zou; Bei Li; Bing Han; Yan Liu; Xueying Wang; Mingshu Bi; Chi-Min Shu (Fuel, 2024)

Preparation technology and preservation mechanism of novel Ag NPs-loaded ZIF-67 packaging film - Lixin Kang; Qiufang Liang; Yuxuan Liu; Arif Rashid; Abdul Qayum; Chengwei Zhou; Xu Han; Xiaofeng Ren; Zhuzhong Chi; Runhao Chi; Haile Ma (Food Packaging and Shelf Life, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

The adaptation of 3T3 cells to simulated microgravity by retrieving the major cell cycle-related protein expression during long-term in vitro proliferation - Chi Nguyen Quynh Ho; Son Nghia Hoang; Hanh Hong Nguyen; Han Thai Minh Nguyen; Han Thi Truong; Quynh Thi Truc Nguyen; Cang Ngoc Ly; Long Thanh Le (Tissue and Cell, 2024)

Seawater Chlorella sp. biofilm for mariculture effluent polishing under environmental combined antibiotics exposure and ecological risk evaluation based on parent antibiotics and transformation products - Chong Yu; Yang Liu; Ying Zhang; Ming-Zhi Shen; Jing-Han Wang; Zhan-You Chi (Science of The Total Environment, 2024)

Co-removal and recycling of Ba2+ and Ca2+ in hypersaline wastewater based on the microbially induced carbonate precipitation technique: Overlooked Ba2+ in extracellular and intracellular vaterite - Huaxiao Yan; Xiaofei Zhu; Zhiyong Liu; Shengping Jin; Jilai Liu; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Maurice E. Tucker; et al. (Journal of Hazardous Materials, 2024)

Elemental differentiation and isotopic fractionation during space weathering of Chang’E-5 lunar soil - Qingshang Shi; Yongsheng He; Jian-Ming Zhu; Yang Wang; Yang Wang; Hongjie Wu; Peijie Wang; Ruyi Yang; Aiying Sun; Yinchu Zhang; Guangliang Wu; Ruoqi Wan; et al. (Geochimica et Cosmochimica Acta, 2024)

Adiponectin attenuates H2O2-induced apoptosis in chicken skeletal myoblasts through the lysosomal-mitochondrial axis - Han Wang; Chi Li; Longbo Zhu; Zhengqun Liu; Ning Li; Zi Zheng; Shiyue Liang; Jun Yan (In Vitro Cellular & Developmental Biology - Animal, 2024)

Chemical, sensory and biological variations of black tea under different drying temperatures - Shengxiao Su; Piaopiao Long; Qing Zhang; Mingchun Wen; Zisheng Han; Feng Zhou; Jiaping Ke; Xiaochun Wan; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2024)

Lamprey VDAC2: Suppressing hydrogen peroxide-induced 293T cell apoptosis by downregulating BAK expression - Mingjian Zhang; Wenwei Li; Xue Zhang; Mengfei Bi; Xinyu Wang; Feng Sun; Jiali Lu; Yan Chi; Yinglun Han; Qingwei Li; Tiesong Li (Fish & Shellfish Immunology, 2024)

Food polyphenols and Maillard reaction: regulation effect and chemical mechanism - Zisheng Han; Mengting Zhu; Xiaochun Wan; Xiaoting Zhai; Chi-Tang Ho; Liang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Targeting the undruggables—the power of protein degraders - Chao Zhang; Yongbo Liu; Guangchen Li; Zhouli Yang; Chi Han; Xiuyun Sun; Chunquan Sheng; Ke Ding; Yu Rao (Science Bulletin, 2024)

Enzymatic impregnation by high hydrostatic pressure for preparing shape-retaining softened broccoli and carrot - Yu-Hsiang Wu; Bo-Chi Huang; Yan-Han Lin; Chung-Yi Wang (Food Bioscience, 2024)

Modulations of ocean-atmosphere interactions on squid abundance over Southwest Atlantic - Chia-Ying Ko; Yu-Chi Lee; Yi-Chi Wang; Huang-Hsiung Hsu; Chun Hoe Chow; Ruei-Gu Chen; Tsung-Han Liu; Chih-Shin Chen; Tai-Sheng Chiu; Don-Hsieh Chiang; Ren-Fen Wu; Wan-Ling Tseng (Environmental Research, 2024)

Effect of Ba2+ on the biomineralization of Ca2+ and Mg2+ ions induced by Bacillus licheniformis - Huaxiao Yan; Xiaofei Zhu; Zhenjiang Li; Zhiyong Liu; Shengping Jin; Xiaotong Zhou; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; et al. (World Journal of Microbiology and Biotechnology, 2024)

Plant Growth Regulatory Activity of Secondary Metabolites Produced by the Invasive Xanthium spinosum’s Endophytic Dematiopleospora sp. - Nigora Kuchkarova; Lijing Lei; Shihong Luo; Zokir Toshmatov; Caixia Han; Shixing Zhou; Chi Zhang; Hua Shao (Journal of Plant Growth Regulation, 2024)

Differences of Escherichia coli isolated from different organs of the individual sheep: molecular typing, antibiotics resistance, and biofilm formation - Zihao Wu; Haoming Chi; Tingting Han; Guangxi Li; Jixue Wang; Wei Chen (Folia Microbiologica, 2024)

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

Selective dissolution of zinc and lead from duplex β-phase brasses in low and high conductivity water - Ming-Han Tsai; Shu-Ju Chao; Cai-lin Luo; Lap-Cuong Hua; Chi-Chang Hu; Biplab Kumar Mahata; Chihpin Huang (Chemosphere, 2024)

Experimental and numerical study of low-yield-point steel corrugated pipe dampers - Hu Li; Yongfeng Du; Jianping Han; Fangyu Li; Peihong Chi (Soil Dynamics and Earthquake Engineering, 2024)

Comparative study of wave height transformation: Bragg reflection versus wave breaking at submerged rectangular breakwaters - Ching-Piao Tsai; Chun-Han Ko; Han-Chen Shih; Yueh-Heng Chen; Ying-Chi Chen (Ocean Engineering, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

TemPanSharpening: A multi-temporal Pansharpening solution based on deep learning and edge extraction - Yifei Han; Hong Chi; Jinliang Huang; Xinyi Gao; Zhiyu Zhang; Feng Ling (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Microalgal-bacterial consortia for the treatment of livestock wastewater: Removal of pollutants, interaction mechanisms, influencing factors, and prospects for application - KhinKhin Phyu; Suli Zhi; Junfeng Liang; Chein-Chi Chang; Jiahua Liu; Yuang Cao; Han Wang; Keqiang Zhang (Environmental Pollution, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Regional differences in sediment oxygen uptake rates in polymetallic nodule and co-rich polymetallic crust mining areas of the Pacific Ocean - Sung-Uk An; Ju-Wook Baek; Sung-Han Kim; Hyun-Min Baek; Jae Seong Lee; Kyung-Tae Kim; Kyeong Hong Kim; Kiseong Hyeong; Sang-Bum Chi; Chan Hong Park (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Cotton-derived three-dimensional carbon fiber aerogel with hollow nanocapsules and ultrahigh adsorption efficiency in dynamic sewage treatment system - Peng Zhang; Lei Zhang; Xiaoyan Yang; Mingming Chi; Yue Han; Zehao Zhang; Changhua Liu; Wubo Wan; Xiaoming Zhao (Bioresource Technology, 2024)

Assessing the Performance of a Dynamical Downscaling Simulation Driven by a Bias-Corrected CMIP6 Dataset for Asian Climate - Zhongfeng Xu; Ying Han; Meng-Zhuo Zhang; Chi-Yung Tam; Zong-Liang Yang; Ahmed M. El Kenawy; Congbin Fu (Advances in Atmospheric Sciences, 2024)

Genetic structure of ten Artemia populations from China: cumulative effects of ancient geological events, climatic changes, and human activities - Ke Li; Rui Zhang; Li-Ying Sui; Chi Zhang; Xue-Kai Han (Frontiers in Marine Science, 2024)
This study investigated the population genetics and distribution patterns of Artemia populations from ten inland salt lakes in China. A total of 1,274,698 Artemia single nucleotide polymorphisms (SNPs) were identified. The results showed that these populations could be geographically and genetically divided into four distinct groups, and that the Tibetan populations were further divided into two subpopulations with a trend of decreasing genetic diversity from west to east. The Tibetan population had the highest genetic diversity, whereas the Shanxi population had the lowest. There was moderate genetic differentiation between the Tibetan populations and greater genetic differentiation between the Xinjiang and Shanxi populations. IBD (isolation by distance) suggested that geographical isolation contributes to genetic differentiation. In addition, there was some degree of gene flow among the ten populations, with A. sinica showing unidirectional gene flow in all populations in the eastern Nagri region. Species distribution modeling showed that mean annual temperature, temperature seasonality, and annual precipitation were the main environmental factors affecting the distribution of Artemia populations and suitable habitats for Tibetan populations will be further reduced in the future. It is necessary to strengthen the protection of germplasm resources and formulate scientific protocols for the sustainable development and utilization of Artemia resources.

Quasi-2D spin-Peierls transition through interstitial anionic electrons in K(NH3)2 - Chi Ding; Qing Lu; Zhaopeng Guo; Tianheng Huang; Junjie Wang; Yu Han; Dingyu Xing; Jian Sun (Science Bulletin, 2024)

Tuning Cu2O morphologies of Cu2O/Ni foam electrodes for the control of reactivity and nitrogen selectivity in direct ammonia electrooxidation reaction - Ming-Han Tsai; Yaju Juang; Chi-Chang Hu; Lap-Cuong Hua; Chihpin Huang (Journal of Environmental Chemical Engineering, 2024)

Activation of peroxymonosulfate by a CuCo-NC diatomic catalyst on N-doped graphene for selective generation of 1O2 towards efficient organic pollutant treatment - Yuxuan Sun; Jie Yu; Xuan Guo; Yuhang Cui; Zijian Zhang; Xiaoyuan Zhang; Shiming Hu; Chenghao Yang; Bo Chi; Kosuke Noborio; Song Han (Journal of Environmental Chemical Engineering, 2024)

Fluid evolution and genesis of the Zhuanghuhe Au–Sb mineralization in the Duobaoshan orefield, Northeast China: Evidence from fluid inclusions and H–O–C isotopes - Han-wen Xue; Ke-yong Wang; Jian-zhen Geng; Si-wen Fan; Jun-chi Chen; Xue Wang (Geochemistry, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Improving impact of heparan sulfate on the endothelial glycocalyx abnormalities in atherosclerosis as revealed by glycan-protein interactome - Qingqing Chen; Xiaohui Xu; Shaoshuai Xie; Anran Sheng; Naihan Han; Zhenyu Tian; Xiaowei Wang; Fuchuan Li; Robert J. Linhardt; Fuming Zhang; Lan Jin; Qunye Zhang; et al. (Carbohydrate Polymers, 2024)

Rapid identification of mushroom toxins by direct electrospray probe mass spectrometry for emergency care - Hung Su; Zong-Han Jiang; Yi-Wen Hsu; Yu-Chi Wang; Yun-Yi Chen; Deng-Chyang Wu; Jentaie Shiea; Chi-Wei Lee (Analytica Chimica Acta, 2024)

Characteristics of fungi formation in urban sewer at different flow conditions: Distribution, metabolism, and pathogenicity - Xuan Shi; Jianshuang Han; Yilian Hui; Yulei Chi; Yuxuan Hou; Xin Jin; Pengkang Jin (Chemosphere, 2024)

Ecotoxicity of three typical tire wear particles to periphytic biofilms: The potentiating role after natural water-incubation-aging - Kun Li; Wanqi Hao; Han Su; Chi Liu; Zhangle Chen; Zidong Ye (Environmental Pollution, 2024)

Experimental verification of seismic vibration control of high-rise buildings with friction-type multiple tuned mass dampers - Ging-Long Lin; Chi-Chang Lin; Tsung-Han Yang; Hao-Yu Lung (Engineering Structures, 2024)

Nocardiosis and other common diseases of cultured golden pompano ( Trachinotus blochii ) in Taiwan - Wei‐Xiao Yan; Yu‐Han Tseng; Wen‐Rou Huang; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Golden pompano ( Trachinotus blochii ) is a carnivorous teleost cultured in the Asia‐Pacific region. Fish culture in high densities and numbers results in disease outbreaks, causing huge economic losses. Here, we collected cultured golden pompanos from 2021 to 2022 and identified the pathogens isolated from the diseased fish. Out of a total of 64 clinical cases observed in both sea cages and fish ponds, it was found that Nocardia seriolae was the predominant pathogen (26%), followed by Lactococcus garvieae (13%). Trichodina spp. was the most prevalent parasite in sea cages and earthen ponds (21%), while Neobenedenia spp. was the primary parasitic pathogen (16%) in sea cages. Given these findings, further investigations were conducted, including antibiotic susceptibility and pathogenicity tests specific to N. seriolae in golden pompanos. Antibiotic susceptibility tests of N. seriolae revealed that all strains were susceptible to doxycycline, oxytetracycline, florfenicol and erythromycin but resistant to amoxicillin and ampicillin. Additionally, a pathogenicity assessment was carried out by administering an intraperitoneal injection of 0.1 mL containing 10 7 CFU of N. seriolae per fish. The mortality rates observed varied between 40% and 90%, with the P2 strain exhibiting the highest level of virulence, resulting in a cumulative mortality of 90%. Therefore, disease outbreaks in fish can be minimized by developing effective treatments and prevention methods.

A multi-modal multi-objective evolutionary algorithm based on dual decomposition and subset selection - Minghui Xiong; Wei Xiong; Zheng Liu; Yali Liu; Chi Han (Swarm and Evolutionary Computation, 2024)

Effects of environmental microplastic exposure on Chlorella sp. biofilm characteristics and its interaction with nitric oxide signaling - Ying Zhang; Jian-Xia Wang; Yang Liu; Jing-Tian Zhang; Jing-Han Wang; Zhan-You Chi (Science of The Total Environment, 2024)

Effects of staged multiple phytohormones application on capillary-driven attached Chlorella sp. biofilm - Chi Li; Jian-Xia Wang; Jing-Han Wang; Zhan-You Chi (Journal of Environmental Management, 2024)

A modified methodology to substitute U-shape well using a single well with fracture network: Design and performance - Lin Jia; Kewen Li; Yun Han; Chi Zhang; Lipeng Zhao (Geothermics, 2024)

Asymmetric response of vegetation GPP to impervious surface expansion: Case studies in the Yellow and Yangtze River Basins - Mingjie Yang; Lianqing Xue; Yuanhong Liu; Saihua Liu; Qiang Han; Lijuan Yang; Yixia Chi (Environmental Research, 2024)

An improved re-entrant honeycomb with programmable densification and multistage energy-absorbing performance - Wei Zhong Jiang; Xing Chi Teng; Xi Hai Ni; Xue Gang Zhang; Xian Cheng; Wei Jiang; Dong Han; Yi Zhang; Xin Ren (Engineering Structures, 2024)

Mn2+ recycling in hypersaline wastewater: unnoticed intracellular biomineralization and pre-cultivation of immobilized bacteria - Huaxiao Yan; Shengping Jin; Xiaolei Sun; Zuozhen Han; Hongmei Wang; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Maurice E. Tucker; Lirong Wei; et al. (World Journal of Microbiology and Biotechnology, 2024)

Investigating the Causes of a Rapid Gravity Decrease at the Luzhou Observatory - Zhongya Li; Yong Wang; Lelin Xing; Minzhang Hu; Yufei Han; Jiansheng Yu; Chi Xiao; Fan Wang; Jiapei Wang; Jian Wang; Xinlin Zhang (Pure and Applied Geophysics, 2024)

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

Bacterial heavy metal resistance related to environmental conditions - Cheng-Han Michael Liu; Hans-Uwe Dahms; Chi-Ying Hsieh; Zong-Ying Lin; Tai-Yan Lin; Xiao-Qian Huang (Chemosphere, 2024)

Microalgal-bacterial biofilms for wastewater treatment: Operations, performances, mechanisms, and uncertainties - Jing-Tian Zhang; Jian-Xia Wang; Yang Liu; Ying Zhang; Jing-Han Wang; Zhan-You Chi; Fan-Tao Kong (Science of The Total Environment, 2024)

Discovery of color compounds: Integrated multispectral omics on exploring critical colorant compounds of black tea infusion - Piaopiao Long; Yaxin Li; Zisheng Han; Mengting Zhu; Xiaoting Zhai; Zongde Jiang; Mingchun Wen; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2024)

Waste polypropylene filter induced synthesis of pure phase Fe3O4 and ZVI incorporated carbon composite for non-radical peroxymonosulfate activation dominated sulfamethoxazole degradation: Singlet oxygen versus electron transfer process - Ying Wu; Chi Song; Xinyan Yu; Xianbao Shen; Lijie Xu; Ying Zhang; Han Gong; Changlei Xia; Lu Gan (Chemical Engineering Journal, 2024)

Water-assisted mass preparation of CsPbBr3-CsPb2Br5-CsPbIxBr3-x composite wafers for high-performance X-ray detection - Yanshuang Ba; Yaoyu Han; Weidong Zhu; Tianran Wang; Jiawei Chi; He Xi; Tianlong Zhao; Dazheng Chen; Jincheng Zhang; Chunfu Zhang; Yue Hao (Chemical Engineering Journal, 2024)

Combined metabolome and transcriptome analysis reveals a critical role of lignin biosynthesis and lignification in stem-like pneumatophore development of the mangrove Avicennia marina - Yu-Chen Zhang; Li-Han Zhuang; Jia-Jie Zhou; Shi-Wei Song; Jing Li; He-Zi Huang; Bing-Jie Chi; You-Hui Zhong; Jing-Wen Liu; Hai-Lei Zheng; Xue-Yi Zhu (Planta, 2024)

Multi-constellation GNSS interferometric reflectometry for tidal analysis: mitigations for K1 and K2 biases due to GPS geometrical errors - Dongju Peng; Yunung Nina Lin; Jui-Chi Lee; Hsuan-Han Su; Emma M. Hill (Journal of Geodesy, 2024)
It has been observed that when using sea levels derived from GPS (Global Positioning System) signal-to-noise ratio (SNR) data to perform tidal analysis, the luni-solar semidiurnal (K2) and the luni-solar diurnal (K1) constituents are biased due to geometrical errors in the reflection data, which result from their periods coinciding with the GPS orbital period and revisit period. In this work, we use 18 months of GNSS SNR data from multiple frequencies and multiple constellations at three sites to further investigate the biases and how to mitigate them. We first estimate sea levels using SNR data from the GPS, GLONASS, and Galileo signals, both individually and by combination. Secondly, we conduct tidal harmonic analysis using these sea-level estimates. By comparing the eight major tidal constituents estimated from SNR data with those estimated from the co-located tide-gauge records, we find that the biases in the K1 and K2 amplitudes from GPS S1C, S2X and S5X SNR data can reach 5 cm, and they can be mitigated by supplementing GLONASS- and Galileo-based sea-level estimates. With a proper combination of sea-level estimates from GPS, GLONASS, and Galileo, SNR-based tidal constituents can reach agreement at the millimeter level with those from tide gauges.

The Role of the Cerebellum in Learning to Predict Reward: Evidence from Cerebellar Ataxia - Jonathan Nicholas; Christian Amlang; Chi-Ying R. Lin; Leila Montaser-Kouhsari; Natasha Desai; Ming-Kai Pan; Sheng-Han Kuo; Daphna Shohamy (The Cerebellum, 2023)

Analysis of PAHs content, source and risk assessment in surface sediments from Laizhou Bay and Bohai Bay - Xusheng Li; Bin Han; Gui Wang; Wei Gao; Li Zheng; Wendan Chi; Yue Shi (Marine Pollution Bulletin, 2023)

Ingestion and biodegradation of disposable surgical masks by yellow mealworms Tenebrio molitor larvae: Differences in mask layers and effects on the larval gut microbiome - Jiaming Wang; Chi Zhang; Xin Zhao; Yue Weng; Xinrui Nan; Xiaoyu Han; Chen Li; Baoqin Liu (Science of The Total Environment, 2023)

Towards resourceful sustainability: Integrating minerals resources in achieving development goals - Zhihong Han; Lixin Gong; Chi Long; Anees Afzal (Resources Policy, 2023)

Unveiling targeted spatial metabolome of rice seed at the dough stage using Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry imaging - Yao Zhao; Jitao Hu; Yilin Zhang; Han Tao; Linying Li; Yuqing He; Xueying Zhang; Chi Zhang; Gaojie Hong (Food Research International, 2023)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Efficient extraction of nanocellulose from lignocellulose using aqueous butanediol fractionation to improve the performance of waterborne wood coating - Xiaoxue Song; Zhipeng Zhu; Sai Tang; Xiang Chi; Guangping Han; Wanli Cheng (Carbohydrate Polymers, 2023)

Effects of acid modified biochar on potassium uptake, leaching and balance in an alternate wetting and drying paddy ecosystem - Hongwei Han; Taotao Chen; Chang Liu; Feng Zhang; Yidi Sun; Yikui Bai; Jun Meng; Daocai Chi; Wenfu Chen (Science of The Total Environment, 2023)

The impact of air pollution on respiratory diseases in an era of climate change: A review of the current evidence - Huan Minh Tran; Feng-Jen Tsai; Yueh-Lun Lee; Jer-Hwa Chang; Li-Te Chang; Ta-Yuan Chang; Kian Fan Chung; Han-Pin Kuo; Kang-Yun Lee; Kai-Jen Chuang; Hsiao-Chi Chuang (Science of The Total Environment, 2023)

Connecting link between a sediment source and its deep-sea sink: Ilan Shelf offshore northeastern Taiwan - Ho-Han Hsu; Char-Shine Liu; John D. Milliman; Tzu-Ting Chen; Jih-Hsin Chang; J. Paul Liu; Chih-Chieh Su; Mei-Chi Fan (Marine and Petroleum Geology, 2023)

Extremely long-lived marine heatwave in South China Sea during summer 2020: Combined effects of the seasonal and intraseasonal variations - Tongxin Han; Kang Xu; Lijuan Wang; Boqi Liu; Chi-Yung Tam; Kai Liu; Weiqiang Wang (Global and Planetary Change, 2023)

Oxidative potential and source apportionment of size-resolved particles from indoor environments: Dithiothreitol (DTT) consumption and ROS production - Kaixing Yao; Sutong Wang; Han Zheng; Xinji Zhang; Yidan Wang; Zihan Chi; Huibin Guo (Atmospheric Environment, 2023)

Uncovering molecular mechanisms involved in microbial volatile compounds-induced stomatal closure in Arabidopsis thaliana - Tu-Trinh Thi Truong; Chi-Chou Chiu; Jing-Yu Chen; Pei-Yu Su; Tri-Phuong Nguyen; Ngoc-Nam Trinh; Tetsuro Mimura; Ruey-Hua Lee; Ching-Han Chang; Hao-Jen Huang (Plant Molecular Biology, 2023)

Analyzing the phosphorus flow characteristics in the largest freshwater lake (Poyang Lake) watershed of China from 1950 to 2020 through a bottom-up approach of watershed-scale phosphorus substance flow model - Wei Liu; Tian Qin; Mengting Wu; Zhiqin Chen; Yalan Zhang; Evgeny Abakumov; Ekaterina Chebykina; Wenjuan Wang; Daishe Wu; Chao Han; Xianchuan Xie; Jiancheng Cheng; et al. (Water Research, 2023)

SERS-based rapid susceptibility testing of commonly administered antibiotics on clinically important bacteria species directly from blood culture of bacteremia patients - Yin-Yi Han; Jann-Tay Wang; Wei-Chih Cheng; Ko-Lun Chen; Yi Chi; Lee-Jene Teng; Juen-Kai Wang; Yuh-Lin Wang (World Journal of Microbiology and Biotechnology, 2023)
Bloodstream infections are a growing public health concern due to emerging pathogens and increasing antimicrobial resistance. Rapid antibiotic susceptibility testing (AST) is urgently needed for timely and optimized choice of antibiotics, but current methods require days to obtain results. Here, we present a general AST protocol based on surface-enhanced Raman scattering (SERS-AST) for bacteremia caused by eight clinically relevant Gram-positive and Gram-negative pathogens treated with seven commonly administered antibiotics. Our results show that the SERS-AST protocol achieves a high level of agreement (96% for Gram-positive and 97% for Gram-negative bacteria) with the widely deployed VITEK 2 diagnostic system. The protocol requires only five hours to complete per blood-culture sample, making it a rapid and effective alternative to conventional methods. Our findings provide a solid foundation for the SERS-AST protocol as a promising approach to optimize the choice of antibiotics for specific bacteremia patients. This novel protocol has the potential to improve patient outcomes and reduce the spread of antibiotic resistance.

Functional traits explain waterbirds' host status, subtype richness, and community‐level infection risk for avian influenza - Shenglai Yin; Ning Li; Wenjie Xu; Daniel J. Becker; Willem F. de Boer; Chi Xu; Taej Mundkur; Nicholas M. Fountain‐Jones; Chunlin Li; Guan‐zhu Han; Qiang Wu; Diann J. Prosser; et al. (Ecology Letters, 2023)
Species functional traits can influence pathogen transmission processes, and consequently affect species' host status, pathogen diversity, and community‐level infection risk. We here investigated, for 143 European waterbird species, effects of functional traits on host status and pathogen diversity (subtype richness) for avian influenza virus at species level. We then explored the association between functional diversity and HPAI H5Nx occurrence at the community level for 2016/17 and 2021/22 epidemics in Europe. We found that both host status and subtype richness were shaped by several traits, such as diet guild and dispersal ability, and that the community‐weighted means of these traits were also correlated with community‐level risk of H5Nx occurrence. Moreover, functional divergence was negatively associated with H5Nx occurrence, indicating that functional diversity can reduce infection risk. Our findings highlight the value of integrating trait‐based ecology into the framework of diversity–disease relationship, and provide new insights for HPAI prediction and prevention.

Fluid evolution and genesis of the Sankuanggou Fe Cu skarn deposit, Duobaoshan ore field, Northeast China: Evidence from fluid inclusions and H-O-S-Pb isotopes - Jun-chi Chen; Ke-yong Wang; Wen-yan Cai; Jian-zhen Geng; Han-wen Xue; Xue Wang (Journal of Geochemical Exploration, 2023)

Direct Z-scheme CoTiO3/g-C3N4 nanoparticles: fabrication and application as a photocatalyst for degradation of tetracycline hydrochloride assisted by peroxydisulfate or peroxymonosulfate under simulated sunlight - Minh-Vien Le; Quynh-Thao-Nhu Nguyen; Ngoc-Diem-Trinh Huynh; Ngoc-Diep Pham; Chi-Hien Truong; Huyen-Tran Tran; Pham-Ngoc-My Le; Triet-Han Ngo; Huu Tai Huynh (Nanotechnology for Environmental Engineering, 2023)

An ultra-sensitive photoelectrochemical sensor for chlorpyrifos detection based on a novel BiOI/TiO2 n-n heterojunction - Ruili Lyu; Yiting Lei; Chi Zhang; Gaiping Li; Runping Han; Lina Zou (Analytica Chimica Acta, 2023)

Indolocarbazole-based small molecules as guest donors for High-Performance ternary organic photovoltaics - Hsiao Han Chiu; Bing-Huang Jiang; Hong Chi Wang; Xuan-Ming Su; Yu-Hsuan Kang; Yu-Wei Su; Hui-Shan Shih; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2023)

Assessment of the impact of local climate zones on fine dust concentrations: A case study from Hanoi, Vietnam - Leen Brusseleers; Vu Giang Nguyen; Kim Chi Vu; Han Huy Dung; Ben Somers; Bruno Verbist (Building and Environment, 2023)

Sediment Instability Caused by Gas Production from Hydrate-bearing Sediment in Northern South China Sea by Horizontal Wellbore: Evolution and Mechanism - Qingchao Li; Difei Zhao; Junkai Yin; Xingyu Zhou; You Li; Peng Chi; Ying Han; Ubedullah Ansari; Yuanfang Cheng (Natural Resources Research, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Tire wear particles in different water environments: occurrence, behavior, and biological effects—a review and perspectives - Kun Li; Han Su; Xiaojia Xiu; Chi Liu; Wanqi Hao (Environmental Science and Pollution Research, 2023)

A sustainable layered nanofiber/sheet aerogels enabling repeated life cycles for effective oil/water separation - Ting Dong; Huabiao Ye; Wenhui Wang; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Risk assessment and binding mechanisms of potentially toxic metals in sediments from different water levels in a coastal wetland - Fusheng Sun; Guanghui Yu; Xingxing Han; Zhilai Chi; Yunchao Lang; Congqiang Liu (Journal of Environmental Sciences, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

Protective effects of esomeprazole against cisplatin-induced ototoxicity: an in vitro and in vivo study - Hanul Jeon; In Sik Song; Jin-Gyeong Park; Hyejin Lee; Eunjung Han; Saemi Park; Yunkyoung Lee; Chi-man Song; Wooyoung Hur; In-Gyun Lee; June Choi (Aquatic Toxicology, 2023)

Quantitative analysis and risk assessment to full-size microplastics pollution in the coastal marine waters of Hong Kong - Yuet-Tung Tse; Hoi-Shing Lo; Chi-Wing Tsang; Jie Han; James Kar-Hei Fang; Sidney Man-Ngai Chan; Eric Tung-Po Sze (Science of The Total Environment, 2023)

Insights into autotrophic carbon fixation strategies through metagonomics in the sediments of seagrass beds - Xiangqun Chi; Zhiyi Zhao; Qiuxia Han; Huaxiao Yan; Bei Ji; Yating Chai; Shengying Li; Kun Liu (Marine Environmental Research, 2023)

Construction of S-scheme p-n heterojunction between protonated g-C3N4 and α-MnS nanosphere for photocatalytic H2O2 production and in situ degradation of oxytetracycline - Yu Wang; Yuxin He; Yujing Chi; Peiji Yin; Lishan Wei; Wenwen Liu; Xinyao Wang; Han Zhang; Haiyan Song (Journal of Environmental Chemical Engineering, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Decomposing the decoupling relationship between energy consumption and economic growth in China's agricultural sector - Jiaxuan Hu; Liang Chi; Liwei Xing; Han Meng; Mengshuai Zhu; Jing Zhang; Jianzhai Wu (Science of The Total Environment, 2023)

Integration of microalgae cultivation and anaerobic co-digestion with dairy wastewater to enhance bioenergy and biochemicals production - Adi Kusmayadi; Chi-Yu Huang; Yoong Kit Leong; Po-Han Lu; Hong-Wei Yen; Duu-Jong Lee; Jo-Shu Chang (Bioresource Technology, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Physicochemical and pozzolanic properties of municipal solid waste incineration fly ash with different pretreatments - Zhen Chen; Jiang-Shan Li; Chi-Sun Poon; Wen-Hao Jiang; Zi-Han Ma; Xin Chen; Jian-Xin Lu; Hao-Xin Dong (Waste Management, 2023)

Electricity market development in Vietnam: Historical trends and future outlooks - Thai-Ha Le; Phoumin Han; Ha-Chi Le; Manh-Tien Bui (Utilities Policy, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

Co-contaminants of ethinylestradiol and sulfamethoxazole in groundwater exacerbate ecotoxicity and ecological risk and compromise the energy budget of C. elegans - Yu-Hsuan Kuo; Chun Ming How; Chi-Wei Huang; Pei-Ling Yen; Chan-Wei Yu; Chun-Han Chang; Vivian Hsiu-Chuan Liao (Aquatic Toxicology, 2023)

Large-scale mapping of new mixed rice cropping patterns in southern China with phenology-based algorithm and MODIS dataset - Qihui Shao; Rendong Li; Juan Qiu; Yifei Han; Dongfeng Han; MiaoMiao Chen; Hong Chi (Paddy and Water Environment, 2023)

Riverine antibacterial resistance gradient determined by environmental factors - Cheng-Han Liu; Yi-Lynne Chuang; Revathi Gurunathan; Chi-Ying Hsieh; Hans-Uwe Dahms (Environmental Science and Pollution Research, 2023)

Using HRMS fingerprinting to explore micropollutant contamination in soil and vegetables caused by swine wastewater irrigation - Wen-Ling Chen; Sih-Yi Yu; Shu-Yen Liu; Sheng-Chi Lin; Tsung-Han Lee (Science of The Total Environment, 2023)

Carnosic acid attenuated cytochrome c release through the mitochondrial structural protein Mic60 by PINK1 in SH-SY5Y cells - Chia-Yuan Lin; Yi-Chen Huang; Chi-Rei Wu; Han-Ting Wu; Ru-Huei Fu; Chia-Wen Tsai (Food and Chemical Toxicology, 2023)

Assessing the impact of rockfall on a bridge by using hybrid DEM/FEM analysis: A case study in Central Taiwan - Terry Y.P. Yuen; Meng-Chia Weng; Yu-Yao Fu; Guan-Ting Lu; Wen-Jie Shiu; Cheng-An Lu; Chun-Yuan Liu; Chia-Chi Chiu; Tzu-Han Wen (Engineering Geology, 2023)

Effects of environment-relevant concentrations of antibiotics on seawater Chlorella sp. biofilm in artificial mariculture effluent - Chong Yu; Chi Li; Ying Zhang; Xiang Du; Jing-Han Wang; Zhan-You Chi; Qian Zhang (Algal Research, 2023)

Classifying Temporomandibular Disorder with Artificial Intelligent Architecture Using Magnetic Resonance Imaging - Zih-Kai Kao; Neng-Tai Chiu; Hung-Ta Hondar Wu; Wan-Chen Chang; Ding-Han Wang; Yen-Ying Kung; Pei-Chi Tu; Wen-Liang Lo; Yu-Te Wu (Annals of Biomedical Engineering, 2023)

Calcium ion removal at different sodium chloride concentrations by free and immobilized halophilic bacteria - Huaxiao Yan; Jiahao Cao; Minhan Teng; Long Meng; Lanmei Zhao; Xiangqun Chi; Zuozhen Han; Maurice E. Tucker; Hui Zhao (Water Research, 2023)

Photothermal and Concus Finn capillary assisted superhydrophobic fibrous network enabling instant viscous oil transport for crude oil cleanup - Ting Dong; Yanhui Liu; Na Tian; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Hydrometallurgy recovery of copper, aluminum and silver from spent solar panels - Qi Han; Yidi Gao; Ting Su; Jiabao Qin; Chi Wang; Zhan Qu; Xianze Wang (Journal of Environmental Chemical Engineering, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Intracellular kynurenine promotes acetaldehyde accumulation, further inducing the apoptosis in soil beneficial fungi Trichoderma guizhouense NJAU4742 under acid stress - Han Zhu; Tuo Li; Chi Li; Yang Liu; Youzhi Miao; Dongyang Liu; Qirong Shen (Environmental Microbiology, 2023)
In this study, the growth of fungi Trichoderma guizhouense NJAU4742 was significantly inhibited under acid stress, and the genes related to acid stress were identified based on transcriptome analysis. Four genes including tna 1, adh 2/4, and bna 3 were significantly up‐regulated. Meanwhile, intracellular hydrogen ions accumulated under acid stress, and ATP synthesis was induced to transport hydrogen ions to maintain hydrogen ion balance. The enhancement of glycolysis pathway was also detected, and a large amount of pyruvic acid from glycolysis was accumulated due to the activity limitation of PDH enzymes. Finally, acetaldehyde accumulated, resulting in the induction of adh 2/4. In order to cope with stress caused by acetaldehyde, cells enhanced the synthesis of NAD + by increasing the expression of tna 1 and bna 3 genes. NAD + effectively improved the antioxidant capacity of cells, but the NAD + supplement pathway mediated by bna 3 could also cause the accumulation of kynurenine (KYN), which was an inducer of apoptosis. In addition, KYN had a specific promoting effect on acetaldehyde synthesis by improving the expression of eno 2 gene, which led to the extremely high intracellular acetaldehyde in the cell under acidic stress. Our findings provided a route to better understand the response of filamentous fungi under acid stress.

Associations between air pollutants and hospital admissions for chronic obstructive pulmonary disease in Jinan: potential benefits from air quality improvements - Chuanlong Cheng; Chuang Han; Qidi Fang; Ying Liu; Xiangyu Chi; Xiujun Li (Environmental Science and Pollution Research, 2023)

Editorial: Oceanographic processes linking nearshore, continental shelf, and shelf break - Feng-Hsun Chang; Yun-Chi Lin; Kuo-Ping Chiang; Ya-Han Nien; Chih-hao Hsieh; Wei-Jen Chen; Chin-Chang Hung; Toru Kobari; Hiroaki Saito; William Savidge (Frontiers in Marine Science, 2023)

Constructing Z-scheme NiMoO4@Co3O4 core-shell heterogeneous architectures with prominent photoelectrocatalytic performance toward water purification - Huijun Li; Pengyuan Wang; Enxi Jin; Wenbo Lan; Chi Han; Guowen Wang; Dezhi Huang; Xinxin Zhang; Hongchao Ma (Chemosphere, 2023)

The long overlooked microalgal nitrous oxide emission: Characteristics, mechanisms, and influencing factors in microalgae-based wastewater treatment scenarios - Ying Zhang; Jing-Han Wang; Jing-Tian Zhang; Zhan-You Chi; Fan-Tao Kong; Qian Zhang (Science of The Total Environment, 2023)

Effects of biohydrogen on premixed charge compression ignition engine operating at various inlet air temperatures - Bingchao Zhao; Xiaoyong Song; Han Wang; Sabariswaran Kandasamy; Arunachalam Chinnathambi; Tahani Awad Alahmadi; Govindasamy Sathiyan; Nguyen Thuy Lan Chi; Rajasree Shanmuganathan (Fuel, 2023)

Passivation of positively charged cationic defects in perovskite with nitrogen-donor crown ether enabling efficient perovskite solar cells - Yuxuan Yang; Tao Zhao; Ming-Hua Li; Xiaoxue Wu; Mingyue Han; Shih-Chi Yang; Qiaoling Xu; Lede Xian; Xiang Chi; Ning-Jiu Zhao; Hong Cui; Sihan Li; et al. (Chemical Engineering Journal, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Corrigendum to “Climate, topography and anthropogenic effects on desert greening: A 40-year monitoring in the Tengger desert, northern China” [Catena 209(2) (2021) 105851] - Li Wang; Yanning Qiu; Zhiyong Han; Chi Xu; Shuang-Ye Wu; Yao Wang; Milena Holmgren; Zhiwei Xu (CATENA, 2023)

Isochrysis sp. cultivation in pilot-scale to concurrently produce sustainable triacylglycerols for human milk fat substitutes and fucoxanthin - Daogui Li; Na Chen; Zhihua Zhou; Cairong Zhong; Jingping Fang; Luqiang Huang; Han Sun; Chengdeng Chi; Youcai Zhou; Yongjin He (Algal Research, 2023)

Control measure implications of COVID-19 infection in healthcare facilities reconsidered from human physiological and engineering aspects - Ying-Fei Yang; Yi-Jun Lin; Shu-Han You; Tien-Hsuan Lu; Chi-Yun Chen; Wei-Min Wang; Chung-Min Liao (Environmental Science and Pollution Research, 2022)

TRG16, targeted by miR-765, inhibits breast cancer stem cell-like properties via regulating the NF-κB pathway - Feng Chi; Xiaoming Jin; Long Chen; Guijin He; Sijia Han (Molecular and Cellular Biochemistry, 2022)

Comparison between culture-positive and culture-negative septic shock in patients in the emergency department - Choon-Bing Chua; Chi-Chieh Hung; Yong-Ye Yang; Tsung-Han Wang; Yin-Chou Hsu (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Assessing the effect of probiotics on tilapia lake virus‐infected tilapia: Transmission and immune response - Ying‐Fei Yang; Jidapa Yamkasem; Win Surachetpong; Yi‐Jun Lin; Shu‐Han You; Tien‐Hsuan Lu; Chi‐Yun Chen; Wei‐Min Wang; Chung‐Min Liao (Journal of Fish Diseases, 2022)
Probiotics have been used to alleviate disease transmission in aquaculture. However, there are limited studies on probiotic use in modulating tilapia lake virus (TiLV). We assessed commercially available probiotic supplements used in TiLV‐infected tilapia and performed mortality and cohabitation assays. We developed a mechanistic approach to predict dose–response interactions of probiotic effects on mortality and immune gene response. We used a susceptible–infected–mortality disease model to assess key epidemiological parameters such as transmission rate and basic reproduction number ( R 0 ) based on our viral load dynamic data. We found that the most marked benefits of probiotics are significantly associated with immune system enhancements (~30%) and reductions in disease transmission (~80%) and R 0 (~70%) in tilapia populations, resulting in a higher tolerance of farming densities (~400 fold) in aquaculture. These findings provide early insights as to how probiotic use‐related factors may influence TiLV transmission and the immune responses in TiLV‐infected tilapia. Our study facilitates understanding the mode of action of probiotics in disease containment and predicting better probiotic dosages in diet and supplements to achieve the optimal culturing conditions. Overall, our analysis assures that further study of rationally designed and targeted probiotics, or mechanistic modelling is warranted on the basis of promising early data of this approach.

Relationships of multiple metals exposure, global DNA methylation, and urothelial carcinoma in central Taiwan - Hui-Tsung Hsu; Hui-Ling Lee; Hsu-Hui Cheng; Chao-Hsiang Chang; Chiu-Shong Liu; Po-Jen Hsiao; Han Chang; Chi-Shun Lien; Mu-Chi Chung; Chi-Jung Chung (Archives of Toxicology, 2022)

Chemical composition and phytotoxic activity of the essential oil of Artemisia sieversiana growing in Xinjiang, China - Chun-Yu Jiang; Shi-Xing Zhou; Zokir Toshmatov; Yu Mei; Guang-Zhao Jin; Cai-Xia Han; Chi Zhang; Hua Shao (Natural Product Research, 2022)

Hypolipidemic effect of chromium-modified enzymatic product of sulfated rhamnose polysaccharide from Enteromorpha prolifera in type 2 diabetic mice - Xinyu Wang; Han Ye; Jiefen Cui; Yongzhou Chi; Ruizhi Liu; Peng Wang (Marine Life Science & Technology, 2022)
Sulfated rhamnose polysaccharide (SRP) derived from Enteromorpha prolifera is a metal-ion chelating agent that could potentially be used to treat diabetes. The aim of our study was to determine the effect of a variant of SRP on DIABETES. First, we synthesized and characterized SRPE-3 chromium(III) [SRPE-3-Cr(III)] complex using an enzymatic method. The maximum chelation rate was 18.2% under optimal chelating conditions of pH 6.0, time 4 h, and temperature 60 °C. Fourier transform infrared spectroscopy results showed important sites for Cr(III)-binding were O–H and C=O groups. We then studied the hypolipidemic effects of SRPE-3-Cr(III) on type 2 diabetes mellitus (T2DM) induced by a high-fat, high-sucrose diet (HFSD). Decreased blood glucose content, body fat ratio, serum TG, TC, LDL-C, and increased serum HDL-C were observed after treatment with SRPE-3-Cr(III). In addition, SRPE-3-Cr(III) significantly reduced leptin, resistin, and TNF-α levels, and increased adiponectin contents relative to T2DM. Histopathology results also showed that SRPE-3-Cr(III) could alleviate the HFSD-lesioned tissues. SRPE-3-Cr(III) also improved lipid metabolism via a reduction in aspartate aminotransferase, alanine aminotransferase, fatty acid synthase, and acetyl-CoA carboxylase activities in the liver. SRPE-3-Cr(III) at low doses exhibited better lipid-lowering activities, hence, could be considered to be a novel compound to treat hyperlipidemia and also act as an anti-diabetic agent.

Bioremediation of decabromodiphenyl ether or benzo(a)pyrene-contaminated rice-paddy soil - Han-Hsin Li; Shu-Chi Chang (Journal of Soils and Sediments, 2022)

Exogenous ABA promotes aroma biosynthesis of postharvest kiwifruit after low-temperature storage - Xueyuan Han; Xiaoyu Wang; Chi Shen; Yiwei Mo; Rungang Tian; Linchun Mao; Zisheng Luo; Huanyi Yang (Planta, 2022)

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Assessment of genetic diversity among Chinese high-oleic peanut genotypes using miniature inverted-repeat transposable element markers - Chuan Tang Wang; Guo Sheng Song; Zhi Wei Wang; Hong Ju Li; Hong Wei Han; Xiao Yuan Chi; Xiu Zhen Wang; Xiu Shan Sun (Genetic Resources and Crop Evolution, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

To roll or not to roll: nyctinastic behavior in young leaves of sacred lotus, Nelumbo nucifera - Can Dai; Xueting Xie; Zhong Han; Xiong Yang; Jianuo Hu; Yuntan Chi (The Science of Nature, 2022)

Research on hoop capacity of composite foundation of discarded rubber tires - Feng-Chi Wang; Jun Li; Zhen-Huan Lin; Pei-Pei Tian; Han-Yu Zhao (European Journal of Environmental and Civil Engineering, 2022)

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Decreased AQP4 Expression Aggravates ɑ-Synuclein Pathology in Parkinson’s Disease Mice, Possibly via Impaired Glymphatic Clearance - Huili Cui; Wenkang Wang; Xinhui Zheng; Danhao Xia; Han Liu; Chi Qin; Haiyan Tian; Junfang Teng (Journal of Molecular Neuroscience, 2021)

Quantitative trait locus mapping and genomic selection of tobacco (Nicotiana tabacum L.) based on high-density genetic map - Zhijun Tong; Zhihui Xiu; Yao Ming; Dunhuang Fang; Xuejun Chen; Yafei Hu; Juhong Zhou; Weiming He; Fangchan Jiao; Chi Zhang; Shancen Zhao; Han Jin; et al. (Plant Biotechnology Reports, 2021)
Tobacco ( Nicotiana tabacum L.) is an economic crop and a model organism for studies of plant biology and genetics. As an allotetraploid plant generated from interspecific hybridization, tobacco has a massive genome (4.5 Gb). Recently, a genetic map with 45,081 single nucleotide polymorphism (SNP) markers was constructed using whole-genome sequencing data for a tobacco population including 274 individuals. This provides a basis for quantitative trait locus (QTL) mapping and genomic selection, which have been widely applied to other crops but have not been feasible in tobacco. Based on this high-density genetic map, we identified QTLs associated with important agronomic traits, chemical compounds in dry leaves, and hazardous substances in processed cigarettes. The LOD values for major QTLs were highest for agronomic traits, followed by chemical compounds and hazardous substances. In addition to the identification of molecular markers, we evaluated genomic selection models and found that BayesB had the highest prediction accuracy for the recombinant inbred line population. Our results offer new insights into the genetic mechanism underlying important traits, such as agronomic traits and quality-related chemical compounds in tobacco, and will be able to support the application of molecular breeding to tobacco.

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Exposure to 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol and risk of thyroid cancer: a case-control study in China - Wan-Jun Yang; Hua-Bing Wu; Chi Zhang; Qi Zhong; Ming-Jun Hu; Jia-Liu He; Guo-Ao Li; Zhen-Yu Zhu; Jin-Liang Zhu; Huan-Huan Zhao; Han-Shuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2021)

Social disruption–induced stress pre-exposure aggravates, while the presence of conspecifics diminishes, acetic acid–induced writhing - Yi-Han Liao; Yi-Chi Su; Yu-Han Huang; Hao Chen; Ya-Hsuan Chan; Li-Han Sun; Chianfang G. Cherng; Ing-Tiau B. Kuo; Lung Yu (Psychopharmacology, 2021)

Effect of dietary supplementation with Chlorella sorokiniana meal on the growth performance, antioxidant status, and immune response of rainbow trout (Oncorhynchus mykiss) - Weijun Chen; Lin Luo; Danxiang Han; Feiping Long; Qinglei Chi; Qiang Hu (Journal of Applied Phycology, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Distinct Characteristics of Odor-evoked Calcium and Electrophysiological Signals in Mitral/Tufted Cells in the Mouse Olfactory Bulb - Han Xu; Chi Geng; Xinzhong Hua; Penglai Liu; Jinshan Xu; Anan Li (Neuroscience Bulletin, 2021)
Fiber photometry is a recently-developed method that indirectly measures neural activity by monitoring Ca 2+ signals in genetically-identified neuronal populations. Although fiber photometry is widely used in neuroscience research, the relationship between the recorded Ca 2+ signals and direct electrophysiological measurements of neural activity remains elusive. Here, we simultaneously recorded odor-evoked Ca 2+ and electrophysiological signals [single-unit spikes and local field potentials (LFPs)] from mitral/tufted cells in the olfactory bulb of awake, head-fixed mice. Odors evoked responses in all types of signal but the response characteristics (e.g., type of response and time course) differed. The Ca 2+ signal was correlated most closely with power in the β-band of the LFP. The Ca 2+ signal performed slightly better at odor classification than high-γ oscillations, worse than single-unit spikes, and similarly to β oscillations. These results provide new information to help researchers select an appropriate method for monitoring neural activity under specific conditions.

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

The cellulose synthase (CesA) gene family in four Gossypium species: phylogenetics, sequence variation and gene expression in relation to fiber quality in Upland cotton - Sujun Zhang; Zhenxing Jiang; Jie Chen; Zongfu Han; Jina Chi; Xihua Li; Jiwen Yu; Chaozhu Xing; Mingzhou Song; Jianyong Wu; Feng Liu; Xiangyun Zhang; et al. (Molecular Genetics and Genomics, 2021)

Spirosoma taeanense sp. nov., a radiation resistant bacterium isolated from a coastal sand dune - Ji Hee Lee; Jong-Hyun Jung; Min-Kyu Kim; Han Na Choe; Chi Nam Seong; Sangyong Lim (Antonie van Leeuwenhoek, 2021)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

A predicted protein functional network aids in novel gene mining for characteristic secondary metabolites in tea plant (Camellia sinensis) - Shihua Zhang; Yong Ma; Rui Zhang; Xiaolong He; Ying Chen; Jingke Du; Chi-tang Ho; Youhua Zhang; Guomin Han; Xiaoyi Hu (Journal of Biosciences, 2020)

Hymenobacter baengnokdamensis sp. nov., Isolated from the Soil of a Crater Lake in Korea - Ji Hee Lee; Min-Kyu Kim; Jong-Hyun Jung; Ho Seong Seo; Jing Zhang; Han Na Choe; Seon Choi; Chi Nam Seong; Sangyong Lim (Current Microbiology, 2020)

Combined effects of green manure returning and addition of sewage sludge compost on plant growth and microorganism communities in gold tailings - Yan-Jun Ai; Fu-Ping Li; Hai-Hong Gu; Xiao-Jie Chi; Xue-Tao Yuan; Dong-Yun Han (Environmental Science and Pollution Research, 2020)

A sensitive and rapid bacterial antibiotic susceptibility test method by surface enhanced Raman spectroscopy - Shijie Fu; Xiwen Wang; Ting Wang; Zhiping Li; Deming Han; Chunsheng Yu; Cui Yang; Han Qu; Hang Chi; Yutian Wang; Song Li; Baihui Tian; et al. (Brazilian Journal of Microbiology, 2020)

Complete genome sequence of Sphingobium sp. strain PAMC 28499 reveals a potential for degrading pectin with comparative genomics approach - So-Ra Han; Sung-Min Jang; Young Min Chi; Byeollee Kim; Sang-Hee Jung; Yung Mi Lee; Jun Uetake; Jun Hyuck Lee; Hyun Park; Tae-Jin Oh (Genes & Genomics, 2020)

Stealth Polymer-Coated Graphene Oxide Decorated Mesoporous Titania Nanoplatforms for In Vivo Chemo-Photodynamic Cancer Therapy - Milan Gautam; Biki Gupta; Zar Chi Soe; Kishwor Poudel; Srijan Maharjan; Jee-Heon Jeong; Han-Gon Choi; Sae Kwang Ku; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2020)

Cerebellar Volume Is Associated with Cognitive Decline in Mild Cognitive Impairment: Results from ADNI - Chi-Ying Lin; Chi-Hua Chen; Sarah E. Tom; Sheng-Han Kuo (The Cerebellum, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Improved landslide assessment using support vector machine with bagging, boosting, and stacking ensemble machine learning framework in a mountainous watershed, Japan - Jie Dou; Ali P. Yunus; Dieu Tien Bui; Abdelaziz Merghadi; Mehebub Sahana; Zhongfan Zhu; Chi-Wen Chen; Zheng Han; Binh Thai Pham (Landslides, 2020)

A Regional Approach of Decadal Assessment of Extreme Precipitation Estimates: A Case Study in the Yangtze River Basin, China - Samiran Das; Dehua Zhu; Chi-Han Cheng (Pure and Applied Geophysics, 2020)

Preparation of an oil suspension containing ondansetron hydrochloride as a sustained release parenteral formulation - Thi-Thao-Linh Nguyen; Van-An Duong; Han-Joo Maeng; Sang-Cheol Chi (Drug Delivery and Translational Research, 2020)

Optimization of air quality monitoring network based on a spatiotemporal-spectrum manifold analysis - Chi-Fang Wang; Ming-Che Hu; Chieh-Han Lee; Hwa-Lung Yu (Stochastic Environmental Research and Risk Assessment, 2019)

Preparation of Ondansetron Hydrochloride-Loaded Nanostructured Lipid Carriers Using Solvent Injection Method for Enhancement of Pharmacokinetic Properties - Van-An Duong; Thi-Thao-Linh Nguyen; Han-Joo Maeng; Sang-Cheol Chi (Pharmaceutical Research, 2019)

Measurement of urinary arsenic profiles and DNA hypomethylation in a case–control study of urothelial carcinoma - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Han Chang; Chiu-Shong Liu; Wei-Ting Jung; Huei-Ju Liu; Saou-Hsing Liou; Mu-Chi Chung; Yu-Mei Hsueh (Archives of Toxicology, 2019)

Effects of cover on soil particle and associated soil nutrient redistribution on slopes under rainfall simulation - Jiamei Sun; Chi-hua Huang; Guannan Han; Yafeng Wang (Journal of Soils and Sediments, 2019)

Effects of a Web-based Health Education Program on Quality of Life and Symptom Distress of Initially Diagnosed Advanced Non-Small Cell Lung Cancer Patients: A Randomized Controlled Trial - Chi-Chin Huang; Han-Pin Kuo; Yueh-E Lin; Shu-Ching Chen (Journal of Cancer Education, 2019)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

First molecular detection of Anaplasma phagocytophilum in the hard tick Rhipicephalus haemaphysaloides in Taiwan - Chi-Chien Kuo; Jing-Lun Huang; Chia-Hao Chien; Han-Chun Shih; Hsi-Chieh Wang (Experimental and Applied Acarology, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Phage Application for the Protection from Acute Hepatopancreatic Necrosis Disease (AHPND) in Penaeus vannamei - Jin Woo Jun; Jee Eun Han; Sib Sankar Giri; Kathy F. J. Tang; Xiaohui Zhou; Luis Fernando Aranguren; Hyoun Joong Kim; Saekil Yun; Cheng Chi; Sang Guen Kim; Se Chang Park (Indian Journal of Microbiology, 2018)

Hot Genes in Schizophrenia: How Clinical Datasets Could Help to Refine their Role - Stefano Porcelli; Soo-Jung Lee; Changsu Han; Ashwin A. Patkar; Diego Albani; Tae-Youn Jun; Chi-Un Pae; Alessandro Serretti (Journal of Molecular Neuroscience, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Impact of the Himalayas on the Meiyu–Baiu migration - Chi-Hua Wu; Ming-Dah Chou; Yu-Han Fong (Climate Dynamics, 2018)

Genetic Variants Within Molecular Targets of Antipsychotic Treatment: Effects on Treatment Response, Schizophrenia Risk, and Psychopathological Features - Marco Calabrò; Stefano Porcelli; Concetta Crisafulli; Sheng-Min Wang; Soo-Jung Lee; Changsu Han; Ashwin A. Patkar; Prakash S. Masand; Diego Albani; Ilaria Raimondi; Gianluigi Forloni; Sofia Bin; et al. (Journal of Molecular Neuroscience, 2018)

Association of lead exposure with cardiovascular risk factors and diseases in Chinese adults - Chi Chen; Qin Li; Xiaomin Nie; Bing Han; Yi Chen; Fangzhen Xia; Hualing Zhai; Ningjian Wang; Yingli Lu (Environmental Science and Pollution Research, 2017)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Performance of IUCN proxies for generation length - Han Chi Fung; Robin S. Waples (Conservation Biology, 2017)
One of the criteria used by the International Union for Conservation of Nature (IUCN) to assess threat status is the rate of decline in abundance over 3 generations or 10 years, whichever is longer. The traditional method for calculating generation length ( T ) uses age‐specific survival and fecundity, but these data are rarely available. Consequently, proxies that require less information are often used, which introduces potential biases. The IUCN recommends 2 proxies based on adult mortality rate, = α + 1/ d , and reproductive life span, = α + z * RL, where α is age at first reproduction, d is adult mortality rate, RL is reproductive life span, and z is a coefficient derived from data for comparable species. We used published life tables for 78 animal and plant populations to evaluate precision and bias of these proxies by comparing and with true generation length. Mean error rates in estimating T were 31% for and 20% for , but error rates for were 16% when we subtracted 1 year ( ), as suggested by theory; also provided largely unbiased estimates regardless of the true generation length. Performance of depends on compilation of detailed data for comparable species, but our results suggest taxonomy is not a reliable indicator of comparability. All 3 proxies depend heavily on a reliable estimate of age at first reproduction, as we illustrated with 2 test species. The relatively large mean errors for all proxies emphasized the importance of collecting the detailed life‐history information necessary to calculate true generation length. Unfortunately, publication of such data is less common than it was decades ago. We identified generic patterns of age‐specific change in vital rates that can be used to predict expected patterns of bias from applying .

Altered miRNA expression in lung tissues of patients with chronic obstructive pulmonary disease - Woo Jin Kim; Jae Hyun Lim; Yoonki Hong; Seok-Ho Hong; Chi Young Bang; Jae Seung Lee; Yeon-Mok Oh; Ju Han Kim (Molecular & Cellular Toxicology, 2017)

Changes in surface energy partitioning in China over the past three decades - Yitian Qian; Pang-Chi Hsu; Chi-Han Cheng (Advances in Atmospheric Sciences, 2017)

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

Effects of rapid ascent on the heart rate variability of individuals with and without acute mountain sickness - Ming Ling Yih; Fang-Chi Lin; Heng-Sheng Chao; Han-Chen Tsai; Shi-Chuan Chang (European Journal of Applied Physiology, 2017)

A self-contained GIM-aided Abel retrieval method to improve GNSS-Radio Occultation retrieved electron density profiles - S. Tulasi Ram; Shin-Yi Su; Lung-Chi Tsai; Chao Han Liu (GPS Solutions, 2016)

Blood cadmium in Chinese adults and its relationships with diabetes and obesity - Xiaomin Nie; Ningjian Wang; Yi Chen; Chi Chen; Bing Han; Chunfang Zhu; Yingchao Chen; Fangzhen Xia; Zhen Cang; Meng Lu; Ying Meng; Boren Jiang; et al. (Environmental Science and Pollution Research, 2016)

Steroid Probes Conjugated with Protein-Protected Gold Nanocluster: Specific and Rapid Fluorescence Imaging of Steroid Receptors in Target Cells - Chi-Yan Tsai; Chun-Wei Li; Jie-Ren Li; Bo-Han Jang; Shu-Hui Chen (Journal of Fluorescence, 2016)

Blood Cadmium Level Associates with Lower Testosterone and Sex Hormone-Binding Globulin in Chinese men: from SPECT-China Study, 2014 - Chi Chen; Ningjian Wang; Xiaomin Nie; Bing Han; Qin Li; Yi Chen; Hualing Zhai; Chunfang Zhu; Yingchao Chen; Fangzhen Xia; Meng Lu; Dongping Lin; et al. (Biological Trace Element Research, 2016)

Survivin silencing and TRAIL expression using oncolytic adenovirus increase anti-tumorigenic activity in gemcitabine-resistant pancreatic cancer cells - Zhezhu Han; Seungha Lee; Suyeon Je; Chi-Yong Eom; Hye Jin Choi; Jae J. Song; Joo-Hang Kim (Apoptosis, 2016)

A novel enterocin T1 with anti-Pseudomonas activity produced by Enterococcus faecium T1 from Chinese Tibet cheese - Hui Liu; Lanwei Zhang; Huaxi Yi; Xue Han; Wei Gao; Chunliang Chi; Wei Song; Haiying Li; Chunguang Liu (World Journal of Microbiology and Biotechnology, 2016)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Cambrian oncoids and other microbial-related grains on the North China Platform - Zuozhen Han; Xiaolei Zhang; Naijie Chi; Mei Han; Jusun Woo; Hyun Suk Lee; Jitao Chen (Carbonates and Evaporites, 2015)

Biodecolorization of recalcitrant dye as the sole sourceof nutrition using Curvularia clavata NZ2 and decolorization ability of its crude enzymes - Chin Hong Neoh; Chi Yong Lam; Chi Kim Lim; Adibah Yahya; Hui Han Bay; Zaharah Ibrahim; Zainura Zainon Noor (Environmental Science and Pollution Research, 2015)

Carbon stock and its responses to climate change in C entral A sia - Chaofan Li; Chi Zhang; Geping Luo; Xi Chen; Bagila Maisupova; Abdullo A. Madaminov; Qifei Han; Bekmamat M. Djenbaev (Global Change Biology, 2015)
Central Asia has a land area of 5.6 × 10 6 km 2 and contains 80–90% of the world's temperate deserts. Yet it is one of the least characterized areas in the estimation of the global carbon (C) stock/balance. This study assessed the sizes and spatiotemporal patterns of C pools in Central Asia using both inventory (based on 353 biomass and 284 soil samples) and process‐based modeling approaches. The results showed that the C stock in Central Asia was 31.34–34.16 Pg in the top 1‐m soil with another 10.42–11.43 Pg stored in deep soil (1–3 m) of the temperate deserts. They amounted to 18–24% of the global C stock in deserts and dry shrublands. The C stock was comparable to that of the neighboring regions in Eurasia or major drylands around the world (e.g. Australia). However, 90% of Central Asia C pool was stored in soil, and the fraction was much higher than in other regions. Compared to hot deserts of the world, the temperate deserts in Central Asia had relatively high soil organic carbon density. The C stock in Central Asia is under threat from dramatic climate change. During a decadal drought between 1998 and 2008, which was possibly related to protracted La Niña episodes, the dryland lost approximately 0.46 Pg C from 1979 to 2011. The largest C losses were found in northern Kazakhstan, where annual precipitation declined at a rate of 90 mm decade −1 . The regional C dynamics were mainly determined by changes in the vegetation C pool, and the SOC pool was stable due to the balance between reduced plant‐derived C influx and inhibited respiration.

Construction of target‐specific virus‐like particles for the delivery of algicidal compounds to harmful algae - Beom Sik Kang; Chi‐Yong Eom; Wonduck Kim; Pyoung il Kim; Sun Yi Ju; Jaewon Ryu; Gui Hwan Han; Jeong‐Il Oh; Hoon Cho; Seung Ho Baek; Gueeda Kim; Minju Kim; et al. (Environmental Microbiology, 2015)
Summary Harmful algal blooms ( HABs ) can lead to substantial socio‐economic losses and extensive damage to aquatic ecosystems, drinking water sources and human health. Common algicidal techniques, including ozonation, ultrasonic treatment and dispersion of algae‐killing chemicals, are unsatisfactory both economically and ecologically. This study therefore presents a novel alternative strategy for the efficient control of deleterious algae via the use of host‐specific virus‐like particles ( VLPs ) combined with chemically synthesized algicidal compounds. The capsid protein of HcRNAV34 , a single‐stranded RNA virus that infects the toxic dinoflagellate, H eterocapsa circularisquama , was expressed in and purified from E scherichia coli and then self‐assembled into VLPs in vitro . Next, the algicidal compound, thiazolidinedione 49 ( TD49 ), was encapsidated into HcRNAV34 VLPs for specific delivery to H . circularisquama . Consequently, HcRNAV34 VLPs demonstrated the same host selectivity as naturally occurring HcRNAV34 virions, while TD49 ‐encapsidated VLPs showed a more potent target‐specific algicidal effect than TD49 alone. These results indicate that target‐specific VLPs for the delivery of cytotoxic compounds to nuisance algae might provide a safe, environmentally friendly approach for the management of HABs in aquatic ecosystems.

Energetics characteristics of the super magnetic storm on November 20, 2003 based on 3D global MHD simulation - JinPeng Han; Chi Wang; Hui Li (Science China Earth Sciences, 2014)

Identification of the Major Sex Pheromone Component of the Scale Insect, Aulacaspis murrayae Takahashi - Hsiao-Yung Ho; Bowroju Suresh Kuarm; Chi-Hung Ke; Yi-Kai Ma; Han-Jung Lee; Chao-Chih Cheng; Kelvin Kwen Liu; Jocelyn G. Millar (Journal of Chemical Ecology, 2014)

Decolourisation of Acid Orange 7 recalcitrant auto-oxidation coloured by-products using an acclimatised mixed bacterial culture - Hui Han Bay; Chi Kim Lim; Thuan Chien Kee; Ismail Ware; Giek Far Chan; Shafinaz Shahir; Zaharah Ibrahim (Environmental Science and Pollution Research, 2014)

A study of earthquake inter-occurrence times distribution models in Taiwan - Chi-Hsuan Chen; Jui-Pin Wang; Yih-Min Wu; Chung-Han Chan; Chien-Hsin Chang (Natural Hazards, 2013)

Application of zeolite-activated carbon macrocomposite for the adsorption of Acid Orange 7: isotherm, kinetic and thermodynamic studies - Chi Kim Lim; Hui Han Bay; Chin Hong Neoh; Azmi Aris; Zaiton Abdul Majid; Zaharah Ibrahim (Environmental Science and Pollution Research, 2013)

Overexpression of the Gossypium barbadense Actin-Depolymerizing Factor 1 Gene Mediates Biological Changes in Transgenic Tobacco - Jina Chi; Yucui Han; Xingfen Wang; Lizhu Wu; Guiyin Zhang; Zhiying Ma (Plant Molecular Biology Reporter, 2013)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

OsWRKY30 is a transcription activator that enhances rice resistance to the Xanthomonas oryzae pathovar oryzae - Muho Han; Hak-Seung Ryu; Chi-Yeol Kim; Dong-Soo Park; Yul-Kyun Ahn; Jong-Seong Jeon (Journal of Plant Biology, 2013)

Biosorption and biodegradation of Acid Orange 7 by Enterococcus faecalis strain ZL: optimization by response surface methodological approach - Chi Kim Lim; Hui Han Bay; Azmi Aris; Zaiton Abdul Majid; Zaharah Ibrahim (Environmental Science and Pollution Research, 2013)

In acute kidney injury, indoxyl sulfate impairs human endothelial progenitor cells: modulation by statin - Vin-Cent Wu; Guang-Huar Young; Po-Hsun Huang; Shyh-Chyi Lo; Kuo-Chuan Wang; Chiao-Yin Sun; Chan-Jung Liang; Tao-Ming Huang; Jou-Han Chen; Fan-Chi Chang; Yuh-Lien Chen; Yih-Shing Kuo; et al. (Angiogenesis, 2013)

Characteristics and genesis of microbial lumps in the Maozhuang Stage (Cambrian Series 2), Shandong Province, China - RenChao Yang; AiPing Fan; ZuoZhen Han; NaiJie Chi; Yu Han (Science China Earth Sciences, 2013)

Identification of a canonical SCFSLF complex involved in S-RNase-based self-incompatibility of Pyrus (Rosaceae) - Chi Xu; Maofu Li; Junkai Wu; Han Guo; Qun Li; Yu’e Zhang; Jijie Chai; Tianzhong Li; Yongbiao Xue (Plant Molecular Biology, 2013)

Combretastatin A-4 derivatives: synthesis and evaluation of 2,4,5-triaryl-1H-imidazoles as potential agents against H1299 (non-small cell lung cancer cell) - Chih-Hua Tseng; Chi-Yi Li; Chien-Chih Chiu; Huei-Ting Hu; Chein-Hwa Han; Yeh-Long Chen; Cherng-Chyi Tzeng (Molecular Diversity, 2012)

Investigation of array-derived rotation in TAIPEI 101 - Chin-Jen Lin; Wen-Gee Huang; Han-Pang Huang; Bor-Shouh Huang; Chin-Shang Ku; Chun-Chi Liu (Journal of Seismology, 2012)

Cyclosporin A induces apoptosis in H9c2 cardiomyoblast cells through calcium-sensing receptor-mediated activation of the ERK MAPK and p38 MAPK pathways - Jinyu Chi; Yejing Zhu; Yu Fu; Yue Liu; Xiaohui Zhang; Lei Han; Xinhua Yin; Dechao Zhao (Molecular and Cellular Biochemistry, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Possible roles of auxin and zeatin for initiating the dwarfing effect of M9 used as apple rootstock or interstock - Hong Li Li; He Zhang; Chi Yu; Li Ma; Yi Wang; Xin Zhong Zhang; Zhen Hai Han (Acta Physiologiae Plantarum, 2012)

Ex situ and in situ measurements of juvenile yellowfin tuna Thunnus albacares target strength - Hsueh-Jung Lu; Myounghee Kang; Hsing-Han Huang; Chi-Chang Lai; Long-Jin Wu (Fisheries Science, 2011)

Data-oriented analyses of ciliate foraging behaviors - Yang-Chi Chang; Jang-Ching Yan; Jiang-Shiou Hwang; Cheng-Han Wu; Meng-Tsung Lee (Hydrobiologia, 2011)

Two-stent strategy for renal artery stenosis with bifurcation lesion - Hong-bing Yan; Bin Zheng; Zheng Wu; Jian Wang; Han-jun Zhao; Li Song; Yun-peng Chi (Journal of Zhejiang University-SCIENCE B, 2010)

Evaluation of suitable reference gene for real-time PCR in human umbilical cord mesenchymal stem cells with long-term in vitro expansion - Youwei Wang; Zhibo Han; Shulin Yan; Aibin Mao; Bin Wang; He Ren; Ying Chi; Zhongchao Han (In Vitro Cellular & Developmental Biology - Animal, 2010)

NMDA receptor antagonist MK-801 reduces neuronal damage and preserves learning and memory in a rat model of traumatic brain injury - Rui-Zhang Han; Jin-Jia Hu; Yuan-Chi Weng; Ding-Feng Li; Yi Huang (Neuroscience Bulletin, 2009)

Effects of chronic 4-n-nonylphenol treatment on aortic vasoconstriction and vasorelaxation in rats - Chi-Ying Hsieh; Chang-Ling Miaw; Chien-Cheng Hsieh; Hui-Ching Tseng; Yuan-Han Yang; Chia-Hung Yen (Archives of Toxicology, 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

Proteomic analysis of rice mutants susceptible to Magnaporthe oryzae - Hak-Seung Ryu; Min-Young Song; Chi-Yeol Kim; Muho Han; Sang-Kyu Lee; Nayeon Ryoo; Jung-Il Cho; Tae-Ryong Hahn; Jong-Seong Jeon (Plant Biotechnology Reports, 2009)

Response mechanisms of antioxidants in bryophyte (Hypnum plumaeforme) under the stress of single or combined Pb and/or Ni - Shou-Qin Sun; Ming He; Tong Cao; You-Chi Zhang; Wei Han (Environmental Monitoring and Assessment, 2009)

Sailing through the Late Pleistocene: unusual historical demography of an East Asian endemic, the Chinese Hwamei ( Leucodioptron canorum canorum ), during the last glacial period - SHOU‐HSIEN LI; CAROL K‐L. YEUNG; JULIE FEINSTEIN; LIANXIAN HAN; MANH HUNG LE; CHI‐XAN WANG; PING DING (Molecular Ecology, 2009)
Pleistocene climate fluctuations shaped the patterns of genetic diversity observed in extant species. In contrast to Europe and North America where the effects of recent glacial cycles on genetic diversity have been well studied, the genetic legacy of the Late Pleistocene for East Asia, a region of great topographical complexity and presumably milder historical climate, remains poorly understood. We analysed 3.86 kb of the mitochondrial genome of 186 Chinese Hwamei birds, Leucodioptron canorum canorum , and found that contrary to the conventional expectation of population decline during cold periods (stadials), the demographic history of this species shows continuous population growth since the penultimate glacial period (about 170 000 years ago). Refugia were identified in the south, coastal regions, and northern inland areas, implying that topographic complexity played a substantial role in providing suitable habitats for the Chinese Hwamei during cold periods. Intermittent gene flow between these refugia during the warmer periods (interstadials) might have resulted in a large effective population of this bird through the last glacial period.

Monitoring of Aerial Pollutants Emitted from Swine Houses in Korea - Ki Y. Kim; Han J. Ko; Hyeon T. Kim; Yoon S. Kim; Young M. Roh; Cheol M. Lee; Chi N. Kim (Environmental Monitoring and Assessment, 2007)

15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) sensitizes human leukemic HL-60 cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through Akt downregulation - Hoon Han; Sung-Won Shin; Chi-Yeon Seo; Hyuk-Chan Kwon; Jin-Yeong Han; In-Hoo Kim; Jong-Young Kwak; Joo-In Park (Apoptosis, 2007)

Hydroquinone–Benzonitrile System: Intramolecular Charge-Transfer and Computational Studies - Kuangsen Sung; Pin-Mei Huang; Chi-Han Zhou (Journal of Fluorescence, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Site-specific phosphorylation of L-form starch phosphorylase by the protein kinase activity from sweet potato roots - Guang-Huar Young; Han-Min Chen; Chi-Tsai Lin; Kuang-Ching Tseng; Jiann-Shing Wu; Rong-Huay Juang (Planta, 2006)

The effect of potato extract used as additive in anther culture medium on culture responses in Triticum aestivum - Jun-Wen Ouyang; Hui Liang; Chi Zhang; Tie-Han Zhao; Shuang-E Jia (Cereal Research Communications, 2004)

Production, purification, and characterization of a novel thermostable serine protease from soil isolate, Streptomyces tendae - Chi-Nam Seong; Jung-Sun Jo; Sang-Ki Choi; Si-Wouk Kim; Sung-Jun Kim; Oh-Hyung Lee; Ji-Man Han; Jin-Cheol Yoo (Biotechnology Letters, 2004)

Synthesis and Cytotoxic Evaluation of a Series of γ-Substituted γ-Aryloxymethyl-α-methylene-γ-butyrolactones Against Cancer Cells - Cheng-Chyi Tzeng; Kuan-Han Lee; Tai-Chi Wang; Chein-Hwa Han; Yeh-Long Chen (Pharmaceutical Research, 2000)